3D Millimeterwellen-Abbildung von dielektrischen Probek?rpern und numerische Rekonstruktion der Materialeigenschaften - Gumbmann, Frank; Weinzierl, Jochen; Tran, Hue Phat; Schmidt, Lorenz-Peter (DGZfP-Jahrestagung Mai, 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.3dmill

3D SAR Processing for a Fast Scanning Millimeter-Wave Short Range Imaging System - Gumbmann, Frank; Tran, Hue Phat; Weinzierl, Jochen; Schmidt, Lorenz-Peter (European Conference on Synthetic Aperture Radar (EuSAR 08,03.-05.06.08), 2008)
A fast scanning short range radar imaging system for security or non-destructive testing applications is presented. The goal was to develop an 3D-imaging system with range independent lateral resolution down to 3 mm and a range resolution down to 6 mm. Therefore a setup with non focusing antennas and a broadband (75-100 GHz) SFCW (stepped frequency continuous wave) radar module were developed. A reconstruction of the device under test (DUT) with high lateral resolution is derived by applying numerical techniques based on the synthetic aperture radar (SAR) principle. To collect as many pixels as possible over a two dimensional aperture a rotating virtual antenna was developed. It is realized by a Gaussian beam transformation of the feed antenna beam waist onto a subreflector. By rotating the quasioptical transformator, an elliptical mirror, the transformed virtual antenna is rotated as well. This scanner concept is applied to planar and cylindrical geometries.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.3dsarp

600 GHz GaAs Schottky Diode Mixer in Split-block Technology - Schür, Jan; Biber, Stephan; Cojocari, O.; Schmidt, Lorenz-Peter; Hartnagel, H. (30th International Conference on Infrared and Millimeter Waves, 2005)
In this paper we present measurement results of a micro-machined split-block waveguide mixer for 600 GHz. The mixer implements a planar GaAs Schottky diode on a quartz substrate. Two different diode designs used for this mixer design are compared. The overall performance of the waveguide mixer is demonstrated by measurements of the mixer in a quasi-optical setup at 600 GHz. In this setup we are able to measure single sideband conversion losses of 9-14 dB at 600 GHz and voltage responsivities of 421-1690 mV/mW. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.600ghz_9
Keywords: 600 GHz; GaAs schottky diode; Heterodyne mixer; Micromachining; Split-block; THz-technology

600 GHz Heterodyne Mixer in Waveguide Technology using a GaAs Schottky Diode - Schür, Jan; Biber, Stephan; Cojocari, O.; Mottet, B.; Schmidt, Lorenz-Peter; Hartnagel, H. (16th International Symposium on Space Terahertz Technology ISSTT, 2005)
In this paper we will present first measurement results for a fixed tuned 600 GHz heterodyne mixer in split-block waveguide technology. The presented mixer design is based on a single planar GaAs Schottky diode which is flip-chip mounted on a quartz substrate. The split-block structure includes an octagonal horn antenna, a waveguide to microstrip transition and a coaxial IF output. In addition to the GaAs diode the quartz substrate includes the required low-pass filter structures which are also used for the DC bias of the diode. The mixer was manufactured by micromechanical milling in brass. With this mixer we were able to measure voltage responsivities up to 1690 V/W and single sideband conversion losses down to 9.4 dB at 600 GHz.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.600ghz
Keywords: heterodyne mixer; split-block; micromachining; 600 GHz; THz-technology; GaAs Schottky diode

600 GHz Waveguide Mixer fabricated by combined conventional and Silicon Micromachining - Schür, Jan; Biber, Stephan; Cojocari, O.; Sydlo, C.; Schmidt, Lorenz-Peter; Hartnagel, H. (Proceedings of the European Microwave Association, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.600ghz_1

A 4th Harmonic Schottky Diode Mixer - Faciliated Access to THz Frequencies - Schür, Jan; Ruf, Marcel; Schmidt, Lorenz-Peter (IRMMW, Passadena / USA, September, 2008)
This paper will present first measurement results of a 4th harmonic Schottky diode mixer operating at 600 GHz. The mixer design compromises a rectangular waveguide based splitblock with an integrated quartz based mixer circuit. A low parasitic planar antiparallel Schottky diode pair is used to downconvert a 600 GHz signal by mixing with the 4th harmonic of the local oscillator. The local oscillator for the presented mixer consists of a 150 GHz PLL-locked frequency doubled Gunn oscillator providing a frequency and phase stabilized LO source for accurate measurements of the magnitude and phase of the RF signal. Simulations predict conversion losses well below 20 dB. Current evaluations of the mixer performance are proving the suitability for short range applications like material characterization and testing as well as for life sciences and medical applications.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.a4thha

A 75 - 110 GHz Seventh-Harmonic Balanced Diode Mixer in a Novel Circuit Configuration - Schneiderbanger, Dirk; Kneuer, C.; Sterns, Michael; Rehner, Robert; Martius, Siegfried; Schmidt, Lorenz-Peter (Proceedings of the 1st European Wireless Technology Conference, 2008)
We report on a novel balanced diode mixer circuit configuration. The mixer operates in a seventh harmonic mixing mode and is fed with the RF signal via a WR-10 waveguide. For a fixed IF of 750 MHz our mixer has very flat characteristics of conversion loss of about 19 dB ± 2.5 dB over the entire W-band (75-110 GHz). The mixer is straight forward to design and its fix-tuned hybrid integrated circuit is easy to manufacture. Only commercially available components are necessary. So our mixer design offers a smart and low-cost alternative solution for broadband receivers as well as for frequency extensions of spectrum analyzers and vector network analyzers. © 2008 EuMA.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.a75110

A Broadband Low Cost Millimeterwave Slotline Detector on Low Permittivity Substrate - Richter, Jürgen; Rehner, Robert; Schmidt, Lorenz-Peter (Proceedings of the European Microwave Conference , Paris, Oct., 2005)
A broadband low cost millimeterwave slotline detector circuit is proposed that can efficiently be realized on a low permittivity substrate (εr = 2.2) which is required for the integration of an antenna. The experimentally approved design achieved a voltage sensitivity of 1660 mV/mW at 77 GHz, with more than 1000 mV/mW between 62 and 85 GHz, a tangential signal sensitivity below -45 dBm and a 1-dB-compression point at -14.8 dBm. The sensitivity is about the same as for commercially available wave-guide detectors despite the unfavourably low substrate permittivity. The compact design and the low cost allow the integration of a larger number of such slotline detectors with antennas on a single substrate for a receiver array in a millimeterwave focal plane imaging system.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.abroad

A Broadband Low Noise Heterodyne Receiver at 2.5 THz - Huber, K.; Brand, Hans; Schmidt, Lorenz-Peter (Proceedings of the 8th International Conference on Terahertz Electronics, 2000)
UnivIS-Import:2015-04-16:Pub.2000.tech.IE.LEH.abroad

A broadband, low noise heterodyne receiver for stratospheric measurements at 2.5 THz - Huber, K; Engelbrecht, Rainer; Hocke, R; Raum, M; Brand, Hans; Martius, Siegfried; Schmidt, Lorenz-Peter (IEEE, 1999)
The LHFT is currently working on a broadband heterodyne receiver for stratospheric measurements at 2.5 THz. Many molecules and radicals such as OH, H/sub 2/O and O/sub 3/ which are involved in the stratospheric ozone chemistry exhibit characteristic emissions in this spectral range. In order to measure these spectra and extract concentration data of the single components, a platform operating at high altitudes is necessary to overcome atmospheric absorption due to water vapor. Research at the LHFT includes the construction of a stable and compact local oscillator (LO) as well as the development of the receiver front end. In the LO subsystem an RF excited grating tunable sealed off CO/sub 2/ laser with an apodized out-coupling element will be used as a pump source. The compact and rugged design is realized by a slab discharge geometry and a metal tube housing. Long term stable gas composition for sealed off operation is optimized during the design phase of the laser by making use of tunable diode laser absorption spectroscopy (TDLAS). A methanol ring-laser with an output power of up to 49 mW at 2522.8 GHz (pump power 20 W) has been developed and is available as a very powerful FIR source. The optimization of the front end concentrates upon broadband and low noise performance. A mixer with newly developed substrate-less Schottky diodes followed by a broadband, noise matched IF-amplifier allow for low noise operation over a frequency range from 6 to about 13 GHz, thus covering emission lines of at least the three species mentioned abov
lhft_intern.bib::thirty_years_LHFT_432

A Broadband, Low Noise Heterodyne Receiver for Stratospheric Measurements at 2.5 THz - Huber, K.; Engelbrecht, Rainer; Hocke, Ralf; Raum, Michael; Brand, Hans; Martius, Siegfried; Schmidt, Lorenz-Peter (Proceedings of IGARSS 99, 1999)
UnivIS-Import:2015-04-16:Pub.1999.tech.IE.LEH.abroad

A Broadband Transition between Dielectric and Planar Waveguides at Millimeterwave Frequencies - Richter, Jürgen; Yazici, Y; Ziegler, Christof; Schmidt, Lorenz-Peter (Proceedings of the 33rd European Microwave Conference, 2003)
A variety of transitions between rectangular dielectric waveguides and planar waveguides like microstrip or slotline have been designed to combine the advantages of dielectric waveguides at millimeterwaves with the excellent hybrid integration capabilities of planar circuits. FDTD field simulations have been applied to analyze and optimize the designed transitions with respect to low insertion and return losses as well as minimized mutual coupling between adjacent transitions. Experimental investigations between 60 and 90 GHz proved the promising results of the simulations with insertion losses between 0.5 and 1.5 dB over the full waveguide band (WR-12). The transitions can well be used for the integration of planar circuits into dielectric waveguides or rod antennas and the designed structures are scalable up to frequencies beyond 100 GHz. © 2003 EUMA.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.abroad

Absolute Phase-Based Distance Measurement for Industrial Monitoring Systems - Schicht, A.; Huber, K.; Ziroff, A.; Willsch, M.; Schmidt, Lorenz-Peter (IEEE Sensors Journal, 2009)
In this paper, principal considerations for a high accuracy millimeter wave (mmw) radar distance measurement system applicable to be used in harsh industrial environments are presented. The system is based on continuous wave (CW) measurement of the reflection coefficient and interpretation of the signal phase. The ambiguity of the phase is overcome by means of a multiple frequency technique. For absolute distance determination, an online calibration procedure is applied. The applicability of the system is underlined by a laboratory demonstrator measurement. © 2009 IEEE.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.LEH.absolu
Keywords: Calibration; Distance measurement; Millimeter wave radar; Multiple frequency continuous wave (CW) radar; Phase measurement

A Compact Fiber-Optic CO and CO_2 Spectrometer: Analysis of Noise, Sensitivity and Lineshapes - Engelbrecht, Rainer; Kuntz, F.; Euring, J.; Krause, M.; Neumann, S.; Schmidt, Lorenz-Peter (4th Int. Conference on Tunable Diode Laser Spectroscopy TDLS 2003, Zermatt, CH, 14.- 18.Juli, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.acompa

A Compact System for Systematic Noise Measurement of Schottky Diodes for THz Applications - Biber, Stephan; Koca, Oe; Huber, K.; Rehm, Guenther; Schmidt, Lorenz-Peter (Conference Proceedings of the European Microwave Week, 2002)
As Schottky diodes still remain the most frequently used devices in THz mixers, precise evaluation of their DC and noise performance is essential for the improvement of mixers in the sub-millimeter wave regime. We present first results from a measurement system which is able to measure the DC characteristics and the noise for Schottky diodes as a function of frequency and bias current. The automated system is capable of contacting many diodes consecutively. © 2002 IEEE.
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.acompa

A Comprehensive Analysis of Quasiplanar Waveguides for Millimeter-Wave Application - Schmidt, Lorenz-Peter (European Microwave Conference, 1981)
Quasiplanar waveguides are analyzed which consist of a thin, partially metallized dielectric substrate inserted in the E-plane of a rectangular waveguide. Several slots or strips in symmetric or non-symmetric positions are allowed on each substrate surface. The analysis is based on a simplified formulation of the spectral domain immittance matrix followed by a Galerkin's method. The analysis has been extended to include the computation of higher order propagating and evanescent modes as well as the characteristic impedances of the dominant modes. Numerical results are presented for various configurations with strips or slots on one or both air-dielectric interfaces illustrating the flexibility of the applied metho
lhft_intern.bib::Schmidt9

A Comprehensive Experimental Characterization of a Far Infrared Ring Laser - Biber, Stephan; Schulz, Roland; Beyer, Matthias; Schmidt, Lorenz-Peter (International Journal of Infrared and Millimeter Waves, 2003)
We examine the possibilities to use a CO2-pumped FIR-ring laser system, which was optimized for operation at 2.5THz, for the generation of other FIR-lines using inethanol as laser-active medium. Five laser lines between 1.7 and 4.8THz were detected and characterized with respect to the maximum achievable output power, beam quality and optimum methanol pressure. Mode patterns for most of the lines were recorded in order to allow easy adjustment of the system and line-identification.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.LEH.acompr
Keywords: Beam Analysis; Far-Infrared-Laser-Design; Mode Analysis; THz-Sources

A Contiguos Ultra-Broadband Planar Diplexer from DC-67 GHz - Rehner, Robert; Reck, Christoph; Schneiderbanger, Dirk; Sterns, Michael; Martius, Siegfried; Schmidt, Lorenz-Peter (International Workshop on Microwave Filters, CNES, Toulouse, France, 16-18 October, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.aconti

A Double-Balanced Diode Mixer with Multi-Decade Bandwidth up to 119 GHz - Schneiderbanger, Dirk; Nezadal, Martin; Sterns, Michael; Rehner, Robert; Martius, Siegfried; Schmidt, Lorenz-Peter (Proceedings of the 1st European Wireless Technology Conference, October, 2008)
We report on a new doubled-balanced diode mixer with multi-decade bandwidth. Our hybrid integrated design is feasible with commercially available components and includes a housing with coaxial connectors. The fundamental mixing conversion loss of our mixer is at most 17 dB from 1 to 46 GHz. Third harmonic mixing conversion loss does not exceed 31 dB between 2 and 119 GHz. Our mixer operates between 500 MHz and 119 GHz with a maximum conversion loss of 31 dB by combining fundamental and third harmonic mixing mode. © 2008 EuMA.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.adoubl

Advanced Broadband Millimetre-Wave Characterization Techniques of Dielectrics - Gumbmann, Frank; Tran, Hue Phat; Weinzierl, Jochen; Schmidt, Lorenz-Peter (9th European Conference on Nondestructive Testing, Berlin, September, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.advanc

Advanced Microwave Imaging - Ahmed, Sherif Sayed; Schießl, Andreas; Gumbmann, Frank; Tiebout, Marc; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (IEEE Microwave Magazine, 2012)
Due to the enormous advances made in semiconductor technology over the last few years, high integration densities with moderate costs are achievable even in the millimeter-wave (mm-wave) range and beyond, which encourage the development of imaging systems with a high number of channels. The mm-wave range lies between 30 and 300 GHz, with corresponding wavelengths between 10 and 1 mm. While imaging objects with signals of a few millimeters in wavelength, many optically opaque objects appear transparent, making mm-wave imaging attractive for a wide variety of commercial and scientific applications like nondestructive testing (NDT), material characterization, security scanning, and medical screening. The spatial resolution in lateral and range directions as well as the image dynamic range offered by an imaging system are considered the main measures of performance. With the availability of more channels combined with the powerful digital signal processing (DSP) capabilities of modern computers, the performance of mm-wave imaging systems is advancing rapidl
lhft_intern.bib::Ahmed2012c

A Fast Scanning W-Band System for Advanced Millimetre-Wave Short Range Imaging Applications - Tran, Hue Phat; Gumbmann, Frank; Weinzierl, Jochen; Schmidt, Lorenz-Peter (IEEE National Radar Conference - Proceedings, 2006)
The paper presents the development of a fast scanning W-Band (75-100 GHz) system and a suitable antenna concept for advanced imaging applications. The goal is to obtain a broadband frequency response from a large target area within a short time period. Two typical approaches for the design of a free space millimetre-wave imaging setup will be discussed. The first approach consists of a focused bistatic measurement setup that includes a combination of a conical horn and a dielectric lens in order to focus the beam. The basic idea of the second approach is to use an unfocused measurement setup employing synthetic aperture radar (SAR) algorithms in order to focus the image numerically. Both measurement setups will be discussed with respect to the capability for fast scanning mm-wave imaging systems. Experimental results on planar test objects demonstrate the performance of the developed W-Band system compared to a commercial vector network analyzer (VN

A fast scanning W-band system for advanced millimetre-wave short range imaging applications - Weinzierl, Jochen; Schmidt, Lorenz-Peter; et al. (3rd European Radar Conference, EuRAD 2006, 2007)
The paper presents the development of a fast scanning W-Band (75-100 GHz) system and a suitable antenna concept for advanced imaging applications. The goal is to obtain a broadband frequency response from a large target area within a short time period. Two typical approaches for the design of a free space millimetre-wave imaging setup will be discussed. The first approach consists of a focused bistatic measurement setup that includes a combination of a conical horn and a dielectric lens in order to focus the beam. The basic idea of the second approach is to use an unfocused measurement setup employing Synthetic Aperture Radar (SAR) algorithms in order to focus the image numerically. Both measurement setups will be discussed with respect to the capability for fast scanning mm-wave imaging systems. Experimental results on planar test objects demonstrate the performance of the developed W-Band system compared to a commercial vector network analyzer (VNA). © 2006 EuMA.

A Fibre-Optic Laser Spectrometer for Sensitive Simultaneous Measurement of CO_2 and CO Gas Concentrations - Engelbrecht, Rainer; Euring, J.; Kuntz, F.; Schmidt, Lorenz-Peter (Proceedings, Sensor 2001 (10th Int. Conf. Sensor 2001, Nürnberg 2001), 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.afibre

A Frequency Selective Surface for Harmonic Suppression in THz-Multipliers - Biber, Stephan; Günther, O.; Bozzi, M.; Perregrini, L.; Fischer, Barbara; Hofmann, Arnd; Jepsen, P. U.; Helmer, Harald; Schmidt, Lorenz-Peter (German Microwave Conference, Ulm, Germany, April, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.afrequ

A Heterostructure Barrier Charge Swing device for Frequency Multiplication at 306 GHz - Nicolae, B.; Ruf, Marcel; Schür, Jan; Schmidt, Lorenz-Peter; Hartnagel, H. (IEEE MTTS Atlanta June, 2008)
A new type of frequency multiplier which is called Heterostructure Barrier Charge Swing (HBCS) is proposed. It concerns a bunch of charge carriers swinging in a trough between heterojunction barriers. The behavior of the device is simulated and experimentally verified. Efficiencies of 27% for tripler and 14% for quintupler operation are predicted. A split-block mount with planar circuitry is presented to prove tripler operation capabilities from 102 GHz to 306 GHz. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.aheter
Keywords: HBCS; Microstrip circuits; Semiconductor heterojunctions; Sub-millimeter wave generation; Waveguide transitions

A hybrid broadband microwave triple balanced mixer based on silicon crossed quad diodes - Hrobak, M.; Stein, Wadim; Sterns, M.; Schramm, M.; Schmidt, Lorenz-Peter (42th European Microwave Week, 2012)
Triple balanced mixers (TBM) are ideally suited for use in heterodyne transceivers with great signal bandwidths. The design and construction of a hybrid broadband TBM based on commercial silicon crossed quad diodes is presented. Broadband planar baluns and the use of balanced edge and broadside coupled striplines allow for covering an RF / LO frequency range of 1 GHz to 35 GHz and at least 10 GHz IF bandwidth, if we claim for up- and downconversion loss values below 15 dB. This is achieved with local oscillator power levels PLO ∈ [10,14] dBm and an input 1 dB compression point of 6 dBm. The paper includes spectral measurement data which are in reasonable agreement with the simulation results that are based on a co-simulation procedure between 3D electromagnetic field (EM) simulations and nonlinear harmonic balance circuit simulations.
lhft_intern.bib::hrobakEumwMix

A Hybrid Broadband Millimeter-Wave Diode Ring Mixer with Advanced IF Extraction Technique - Schneiderbanger, Dirk; Cichy, A.; Rehner, Robert; Martius, Siegfried; Sterns, Michael; Schmidt, Lorenz-Peter (Proceedings of the 37th European Microwave Conference, 2007)
We report on a hybrid octave-bandwidth millimeterwave diode mixer with advanced IF extraction. The design uses a reproducible, low cost hybrid technology including thinfilm circuit and flip-chip mounted diode chips. Side coupled Marchand baluns with IF tap provide balanced RF and LO signals as well as serve for extracting the IF signal. Measurement results for fixed, low IF frequency show a conversion loss around 10 dB from 35 to 67 GHz. Furthermore the mixer is suitable for IF frequencies up to 23 GHz. These features allow very flexible applications of the presented mixer in broadband test and measurement systems. © 2007 EuMA.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.ahybri

A Modular Vector Field Measurement System at 150 GHz, 300 GHz and 450 GHz - Hofmann, A.; Seibert, Günter; Manglberger, M.; Kalb, A.; Göbel, S.; Yao, S.; Weinzierl, Jochen; Schmidt, Lorenz-Peter; Brand, Hans (Proceedings of GeMiC, April, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.amodul

A monolithically stabilized voltage controlled oscillator for the millimeter wave range - Güttich, U.; Dieudonne, J.; Schmidt, Lorenz-Peter (1993)

A Multi-channel Frequency-variable Test Signal Generator for SSR Signals - Trommer, Ralph; Quednau, Philipp; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Secondary surveillance radar is an important part of air traffic control nowadays. Modern receivers use an antenna array to estimate the direction of the arriving signal in order to increase the reliability of the received aircraft positions. In this paper a versatile multi-channel signal generator for testing these receivers is presented. The requirements for such a system are explained followed by the description of the hardware and software design and the automatic self calibration process. Finally the measurement results of the output signals are presented. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.amulti

A Multi-Channel Radiometer with Focal Plane Array Antenna for W-Band Passive Millimeterwave Imaging - Richter, Johannes; Nötel, D.; Klöppel, F.; Huck, J.; Essen, H.; Schmidt, Lorenz-Peter (IEEE, IMS 2006, Juni, 2006)
Passive millimeter wave imaging can complement security measures in scenarios such as airports or checkpoints, due to the fact that these frequencies penetrate clothes and enable e.g. concealed weapon detection (CWD). Such a radiometric system has to meet several key requirements concerning its thermal and spacial resolution and the image acquisition time. The latter can be reduced significantly by scanning the scene with multiple beams simultaneously, The demonstrator system presented in this paper describes a multi-channel focal plane array (FPA) approach that cuts the overall scanning time down by a factor of four. Dielectric rod antennas are proposed as feed elements in high density arrays. The dielectric wide angle lens of the FPA is focused at a distance of 20 m for stand-off measurements. Besides addressing the design and characterization of both the antenna setup and the radiometric receivers, measurement results are presented to demonstrate the feasibility of the multi-channel concept. © 2006 IEEE.
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.amulti

A new Structural Approach for Uniform Sub-Micrometer Anode Metallization of Planar THz Schottky Components - Cojocari, O.; Mottet, B.; Rodriguez-Girones, M.; Biber, Stephan; Marchand, L.; Schmidt, Lorenz-Peter; Hartnagel, H. (Semiconductor Science and Technology, 2004)
This paper presents the evaluation of a Schottky contact technology based on electrochemical metal deposition. The results of a long-term systematic investigation and optimization of the anode formation process to improve the yield and performance of Schottky-based GaAs mixer diodes are detailed. Surface preparation prior to the Schottky-metal deposition and anode metallization as previously optimized for whisker-contacted diodes are successfully transferred to the fabrication of planar structures. This uses an auxiliary honeycomb array of anode-like structures called 'dummy anodes', which are processed simultaneously with the real anodes and then removed in the later technological processes. Consequently, the scattering of planar diodes electrical parameters is significantly reduced and the yield of the fabrication process increases from about 5% up to about 50%. Very good dc characteristics such as series resistance (R s) below 8 Ω, ideality factor (η) below 1.2 and saturation current (I sat) of the order of 10 -17 A are achieved for the anode diameter as small as 1 μm. An excellent IF-noise figure of 250 K at 4.8 GHz up to 280 K at 2.1 GHz with current bias up to 3 mA is obtained for non-cooled THz mixer planar diodes. The use of this technological approach has enabled the extraction of statistically significant data which have been used to characterize the criticality of each step of the fabrication process on the device performance.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.LEH.anewst

A New Switch Correction Method for a Single-Receiver VNA - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter (Proceedings of the 43th European Microwave Week, 2013)
Single receiver vector network analyzers (VNA) are offering a cost efficient possibility to measure complex scattering parameters. One main drawback of this architecture is the larger required period of time to complete the measurement, due to the sequential capturing of the wave quantities. In order to reduce this handicap, a new switch correction scheme is detailed in this paper. The discussion includes a comparison to alternative methods based on measurements and simulations. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.anewsw

An Octave-Bandwidth Double-Balanced Millimeter-Wave Mixer - Schneiderbanger, Dirk; Cichy, A.; Rehner, Robert; Martius, Siegfried; Sterns, Michael; Schmidt, Lorenz-Peter (Proceedings of the 36th European Microwave Conference, 2006)
The paper reports on an octave-bandwidth double-balanced mixer which operates in the millimeter-wave range from 35 to 70 GHz. The design uses a low cost hybrid technology: A thin-film circuit is fabricated on an alumina substrate, and the diodes are flip-chip mounted. Balanced signals are provided by side coupled Marchand baluns. As a result the conversion loss averages out at 13 dB
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.anocta

An Octave Bandwidth Finline Frequency Tripler - Hrobak, Michael; Sterns, M.; Stein, Wadim; Schramm, Marcus; Schmidt, Lorenz-Peter (6th German Microwave Conference, 2011)
In this paper a nearly octave bandwidth frequency tripler based on bilateral finlines is presented. The tripler covers the frequency range from 23 GHz to 40 GHz. The achieved conversion loss averages out at 17 dB. Design and test data of the tripler using antiparallel Schottky diodes are reported. A low cost, easy-to-handle Arlon AD1000 high frequency laminate substrate, processed by rapid prototyping laser decompositioning technique is used. The tripler design flow is based on cooperative-simulation using commercially available 3D fullwave and harmonic balance circuit solvers. A comparison of simulation results and measurement data is given. The impact of the ambiguity at defining the characteristic impedance of the hybrid finline on the simulation results is discussed.
lhft_intern.bib::Hrobak11

A novel active real-time digital-beamforming imager for personnel screening - Ahmed, S. S.; Schießl, Andreas; Schmidt, Lorenz-Peter (EUSAR 2012, 2012)
Personnel screening is an essential requirement nowadays for securing air traffic as well as critical infrastructures. Several passive and active imaging systems based on millimeter wave technologies were developed to address the demanded security needs. A novel active near-field imager based on two-dimensional sparse array architecture combined with digital-beamforming technique is demonstrated here. The system is fully electronic, and hence operates in real-time to deliver fully focused three-dimensional images of high dynamic range and resolution. A 2 m times 1 m imager is built and demonstrated full agreement with the theoretical design. The imaging concept, measurement technique, and various imaging results are presented.
lhft_intern.bib::Ahmed2012a

A Novel DGS-Marchand balun from 40 to 80 GHz with IF-tap for mixer design - Rehner, Robert; Schneiderbanger, Dirk; Sterns, Michael; Martius, Siegfried; Schmidt, Lorenz-Peter (IEEE MTT-S International Microwave Symposium July, 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.anovel

A Novel Fabrication Process for Printed Antennas Integrated in Polymer Multi-Layer Car Body Panels - Kilian, Andreas; Schmidt, Lorenz-Peter (Proceedings of the 39th European Microwave Conference, 2009)
The complete fabrication process for the construction of printed millimeter-wave antennas integrated in plastic multi-layer car body panels is presented. Starting from material characteristics and fixed parameters obtained by the investigation of single process steps, the design of microstrip patch antennas at 24GHz will be demonstrated. The fabrication is based on the hot embossing technology for the metallization of a polymer film used as antenna substrate. The antenna feed is realized by laser processing the ground plane, drilling the substrate and via connecting to the back side. The antenna is embedded within the plastic multi-layer structure by laminating a paint foil and reinforcing the part by back injection molding. The comparison between simulation and measurement results gives information about the realizability of plastic integrated millimeter-wave antennas and criteria for future design revisions. Far-reaching potentials of this process are associated with the construction of conformal integrated antenna arrays for automotive radar applications. © 2009 EuMA.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.anovel

A Novel Fully Electronic Active Real-Time Imager Based on a Planar Multistatic Sparse Array - Ahmed, Sherif Sayed; Schiessl, Andreas; Schmidt, Lorenz-Peter (IEEE Transactions on Microwave Theory and Techniques, 2011)
lhft_intern.bib::ahmed2011

A Novel System for Systematic Microwave Noise and DC Characterization of Terahertz Schottky Diodes - Biber, Stephan; Cojocari, O.; Rehm, Guenther; Mottet, B.; Rodriguez-Girones, M.; Schmidt, Lorenz-Peter; Hartnagel, H. (IEEE Transactions on Instrumentation and Measurement, 2004)
An automated system is developed to evaluate a large number Schottky diodes for terahertz applications with respect to their dc and noise characteristics using a highly sensitive noise measurement technique for one port devices. An extensive RF switching matrix allows noise characterization of one port devices at selected frequency points over a bandwidth from 2 to 8 GHz. The measurement principle also accounts for the impedance mismatch between the system and the device under test (DUT). Furthermore, the setup includes an automated three-axis nanopositioning system capable of consecutively contacting many Schottky diodes arranged in a honeycomb array. The highly accurate positioning of the DUT allows to create reproducible contacts with the diodes using electrochemically etched whisker tips. The smooth contacting procedure enables several hundred contacts with the same whisker tip. With this system, we evaluate the statistical distribution of dc and noise parameters of Schottky diodes with an anode diameter of 1 μm within one honeycomb chip. The system helps in optimizing the production parameters of Schottky diodes for terahertz frequencies.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.LEH.anovel
Keywords: Noise; Schottky diodes; Terahertz (THz)

Antenna Concept for an Automotive Radar Sensor at 150 GHz - Köhler, Mike; Schür, Jan; Schmidt, Lorenz-Peter (IEEE Radio Wireless Week 2013, 20-23 Jan., 2013)
Current Automotive Radar sensors operate in a frequency range up to 81 GHz to provide distance, velocity and angle information about traffic objects. For detecting weakly reflecting objects in presence of a nearby strong reflector (e.g. a person standing close to a van) there are high demands on a radar systems angular resolution. A possibility to improve the angular resolution is increasing the operation frequency. In this paper an antenna concept at 150 GHz is presented showing the benefits of high resolution radar for cars. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.antenn

An X-band phased array microwave/photonic beamforming network - Kirsch, Fabian; Banerjee, S.; Zimmer, G.; Feldle, H.; Marten, P.; Schmidt, Lorenz-Peter (1993)

Applicability of the AM-PM Conversion Method to Beam Position Monitoring of Electron Beams accelerated in S-Band Frequency Range - Ruf, M.; Quednau, Philipp; Schmidt, Lorenz-Peter; Setzer, S. (10th European Workshop on Beam Diagnostics and Instrumentation for Particle Accelerators, DIPAC2011, 2011)
lhft_intern.bib::Ruf11

Application of selected performance test scenarios on multi-channel UHF receivers - Trommer, Ralph; Quednau, Philipp; Schmidt, Lorenz-Peter (GeMiC 2016 - The 10th German Microwave Conference (GeMiC 2016), 2016)
In a preceding paper a multi-channel test signal generator for UHF radar applications was presented. The present contribution shows the application of this generator to test the performance of multi-channel receivers in selected scenarios. Exemplary measurement results are presented showing the usable dynamic range and the maximum packet reception rate for a secondary surveillance radar receiver and a smart meter data collector. Furthermore the direction-of-arrival estimation precision and the source separation capabilities of the receivers are tested under various conditions.
lhft_intern.bib::Trommer2016a

Application of Silicon Micromachining Techniques for the Manufacturing of New Passive THz-Components - Biber, Stephan; Schür, Jan; Schmidt, Lorenz-Peter (German Microwave Conference, Karlsruhe, March, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.applic

A Quasi-Lumped Ultra Broadband Contiguos SSL-Diplexer from DC to 80 GHz - Rehner, Robert; Sterns, Michael; Schneiderbanger, Dirk; Martius, Siegfried; Schmidt, Lorenz-Peter (IMS 2009, Boston, June, 2009)
A contiguous planar diplexer in suspended stripline technology with ultrawideband channels from DC to 40 GHz and 40 GHz to 80 GHz is presented. The design of the diplexer is based on quasi-complementary LC lowpass and highpass prototypes which are directly transformed into transmission line elements by using a quasi-lumped approach. This very straightforward design procedure requires no susceptance annulling networks and no introduction of unit elements which could limit the diplexer's operation bandwidth. For achieving an optimal compatibility with external circuits, an ultra-broadband SSL-MSL (suspended stripline - microstrip line) transition with a return loss of more than 18 dB from DC to 83 GHz was designed. The realized diplexer is extremely compact (6times4.5mm) and features a return loss of more than 12 dB from DC to 81 GHz with very low channel insertion losses of typically less than 1 dB after proper optimization.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.aquasi

A Quasioptical Bandpass Filter for 300 GHz on an Electrically thick Silicon Substrate - Biber, Stephan; Bozzi, M.; Günther, O.; Perregrini, L.; Schmidt, Lorenz-Peter (International Microwave Symposium IMS, Long Beach, USA, June, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.aquasi

A Simplified Method for Measuring Complex S-Parameters Dedicated to Synthetic Instrumentation - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter; Lechner, A. (EUMW / EUMC, Paris, October, 2010)
The constantly emerging market for high and medium volume test applications in the area of high frequency devices calls for cost efficient test solutions. One way to achieve this is using modular reconfigurable measurement equipment, thus enabling the reuse of hardware. This tendency brought up some synthetic instruments capable of sophisticated high frequency measurements up to 6 GHz. One feature those COTS-(Commercial Off The Shelf) systems are lacking, is the ability to measure complex scattering parameters. This article introduces an architecture of a synthetic VNA (Vector Network Analyzer) that enables a cost efficient way of measuring S-Parameters. The theoretical basics, a simulation based accuracy estimation as well as first measurement results are presented as proof of concept.
lhft_intern.bib::Schramm10

A Small Size Low Cost Electronically Tunable Bandpass Filter with Integrated Bias Control - Quednau, Philipp; Trommer, Ralph; Schmidt, Lorenz-Peter (International IEEE Conference on Microwaves, Communications, Antennas and Electronic Systems 2013, 2013)
This paper presents the development of a compact sized, low cost wide range tunable bandpass filter based on a novel RF structure. The proposed design offers a narrow passband with a relative bandwidth down to 3.9 %, a wide tuning range from 700 MHz to 1150 MHz and the ability to adapt bandwidth and insertion loss during operation. Tuning is achieved by reverse biased varactor diodes with a low supply voltage of 5 V max. Design of the novel bandpass structure, integration and miniaturization to reduce its size down to approx. 6 cm 2 is discussed. Measurement results over the whole tuning range are presented and the design of a miniaturized multi channel bias controller for easy frequency setting and temperature compensation is described. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.asmall

A SOLR calibration procedure for the 16-term error model - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter (42th European Microwave Week, 2012)
Scattering parameter measurements in the presence of crosstalk is a well documented problem. The available calibration methods, suited for the general 16-term error model, capable of taking the crosstalk into account, suffer from the required Thru-Standard, which has to be perfectly known. This information is hard to acquire in some cases. An approach which makes the advantage of the 7-term SOLR (Short-Open-Load-Reciprocal) accessible to the 16-term error model is discussed in this article. The mathematical description, the feasibility for multiport applications, measurement results and a brief sensitivity analysis will be presented.
lhft_intern.bib::Schramm2012

A Technology Demonstrator for a 0.5 m x 0.5m Fully Electronic Digital Beamforming mm-Wave Imaging System - Schießl, Andreas; Ahmed, S. S.; Genghammer, A.; Schmidt, Lorenz-Peter (EuCAP 2011, 2011)
This paper describes a demonstrator for a millimeter-wave imaging system, showing for the first time the feasibility of an active fully electronic imaging system in the 80 GHz region using a 2D planar sparse array as an imaging sensor. The demonstrator is capable of capturing images of living persons. In this work, the requirements regarding measurement speed are derived. The system architecture is described in detail using block diagrams. The reference channel concept, the signal distribution network, the modular architecture and the ADC / signal processing concepts are explained. Selected measurement results of key system parameters are presented. mm-Wave images of living persons are shown, including examples demonstrating the effects of movement during the measurement.
lhft_intern.bib::Schiessl11a

Automated Synthesis of Shaped Beam Antenna Patterns with Implied Cross Coupling - Reck, C.; Berold, Ulrich; Schmidt, Lorenz-Peter (EuCAP, 2010)
In the following a numerical method to synthesize arbitrary antenna beamshapes of a phase and amplitude controlled array is described. A 25 year old method by Orchard, Elliot et al. is extended to include cross coupling between array elements as well as the single element characteristics. It is shown that the resulting beamshape provides a closer fitting to the desired beamshape function than the original approach at a reasonable computational burden.
lhft_intern.bib::Reck10

Automated threat detection and characterization with a polarimetric multistatic imaging system - Cenanovic, Amir; Gumbmann, Frank; Schmidt, Lorenz-Peter (EUSAR 2012, 2012)
In the field of security technology personnel screening systems are required, which provide detection and characterization of concealed items. This paper presents an approach for the detection and characterization of threats. It is based on the measurement with a polarimetric, multistatic imaging system, which operates in the frequency range of 75–95 GHz. Dielectric objects are identified and estimation of their material parameters is performed, by analyzing the co-polarization components of the polarimetric Sinclair matrix with the reflection ellipsometry method. The cross-polarization components of the scattering matrix are utilized, in order to implement an edge detection. The results show, that the analysis of the polarimetric imaging data represents a promising approach for an automated threat detection, without any invasion of personal privacy. Furthermore, it allows the estimation of the material parameters with a good accuracy.
lhft_intern.bib::Cenanovic2012

Automatic Detection of Concealed Dielectic Objects for Personnel Imaging - Ahmed, S. S.; Ostwald, O.; Schmidt, Lorenz-Peter (IEEE MTT-S International Microwave Workshop on Wireless Sensing, Local Positioning, and RFID (IMWS 2009 - Croatia), 2009)
A technique for the automatic detection of concealed dielectric objects carried by persons is presented. The method is applicable for microwave personnel scanners with sufficient signal bandwidth and is expected to resolve the trade-off with the privacy of the scanned persons, allowing for efficient detection without the need for a human operator. Algorithm description along with measurement results in W-band are presented.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.automa

Automotive Radar Frequencies above 100 GHz and Their Advantages (W24) - Köhler, Mike; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.automo

Automotive Radar Operation Considerations and Concepts at Frequencies beyond 100 GHz - Köhler, Aaron; Hasch, J.; Gumbmann, Frank; Schmidt, Lorenz-Peter; Schür, Jan; Bloecher, H.-J. (Automative Radar Sensors in the 76-81 GHz Frequency Range, EuMW, 2010)
lhft_intern.bib::Koehler10a

A Vector Field Measurement System for 150 GHz - Weinzierl, Jochen; Schulz, Roland; Brand, Hans; Schmidt, Lorenz-Peter (25th International Conference on Infrared and Millimeter Waves, 2000)
The paper describes the design and realization of a heterodyne vector field measurement system. The system is designed to work in a frequency range from 148 GHz to 152 GHz with a dynamic range of about 75 dB and a phase uncertainty better than 3 degrees. It uses two channels for the measurement of the magnitude as well as the phase characteristics of an electromagnetic field. Two fundamental mixers at 150 GHz have been installed, which are both pumped by a 150 GHz phase locked solid-state oscillator unit. The system can be extended to the 300 GHz and 450 GHz frequency range by replacing these mixers by subharmonically pumped mixers. The mixers and two dielectric antennas, used as distortion minimized field probes, are mounted on a high precision 3D scanning platform. At the IF frequency of 160 MHz the vector analysis of the measured signals is done by an IF processing unit with considerably enhanced measurement accuracy by software corrections with a personal computer.
UnivIS-Import:2015-04-16:Pub.2000.tech.IE.LEH.avecto

A Waveguide to Differential Stripline Transition for Planar mm Wave Antenna Measurements - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (Global Symposium on Millimeter Waves, GSMM, 2011)
lhft_intern.bib::Methfessel11

Bandpass Filter with Tuneable Bandwidth and Center Frequency basedon Varactor Diodes - Reck, C; Trommer, Ralph; Schmidt, Lorenz-Peter (6th German Microwave Conference, 2011)
lhft_intern.bib::Reck2011a

Beam Position and Energy Monitoring in Compact Linear Accelerators for Radiotherapy - Ruf, Marcel; Mueller, Sven; Setzer, Stefan; Schmidt, Lorenz-Peter (IEEE Transactions on Biomedical Engineering, 2014)
The experimental verification of a novel sensor topology capable of measuring both the position and energy of an electron beam inside a compact electron linear accelerator for radiotherapy is presented. The method applies microwave sensing techniques and allows for the noninterceptive monitoring of the respective beam parameters within compact accelerators for medical or industrial purposes. A state space feedback approach is described with the help of which beam displacements, once detected, can be corrected within a few system macropulses. The proof-of-principle experiments have been conducted with a prototype accelerator and customized hardware. Additionally, closed-loop operation with high accuracy is demonstrated. © 2013 IEE
UnivIS-Import:2015-03-09:Pub.2014.tech.IE.LEH.beampo
Keywords: Beam diagnostics; capacitive sensors; electron accelerators; linear accelerators; microwave sensors; state feedback

Beam Position Monitoring Based on Higher Beam Harmonics for Application in Compact Medical and Industrial Linear Electron Accelerators - Ruf, Marcel; Schmidt, Lorenz-Peter; Setzer, S. (1st International Particle Accelerator Conference, IPAC10, 2010)
lhft_intern.bib::Ruf10a

Beam Position Monitoring based on RF Heterodyning and Log-Ratio Signal Processing for Electron Accelerator Systems - Ruf, Marcel; Schmidt, Lorenz-Peter; Setzer, S. (41st European Microwave Conference, 2011)
(BPM) and control is presented. For the first time, the combination of conventional BPM hardware and individually designed RF circuitry for S-Band accelerators is investigated and its applicability to beam position measurements is validated. The concept is based on heterodyning higher harmonics of the beam spectrum and processing them by means of the log- ratio technique. Measurement results gathered with an 8-channel receiver module and a test stand, based on a 6 MeV electron beam, are also presented.
lhft_intern.bib::Ruf11a

Berechnung der Leitungsparameter quasiplanarer Wellenleiter fuer integrierteMillimeterwellen-Schaltungen - Schmidt, Lorenz-Peter; Menzel, W (Wissenschaftliche Berichte AEG Telefunken, 1981)
lhft_intern.bib::Schmidt7

Body Scanner Using Active Imaging - Adametz, Julian; Schmidt, Lorenz-Peter (IMS 2013 Workshop on Microwave Systems for Security Applications, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.bodysc

Breitbandige Finleitungs-Richtkoppler - Callsen, H; Schmidt, Lorenz-Peter; Solbach, K (Wissenschaftliche Berichte AEG Telefunken, 1981)
lhft_intern.bib::Schmidt8

Broadband Detector Array Concept for 3D Holographic Imaging at THz Frequencies - Schildbach, Christian; Schür, Jan; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
A field coupled detector is presented including planar antenna design as well as the video amplifier topology. The compact antenna design is suitable for application in dense antenna arrays. Particularly an array concept is shown that suits for holographic imaging at frequencies beyond 200 GHz. For this purpose a broadband planar antenna is designed for frequencies from 230 GHz to 325 GHz, allowing for high depth resolution in an imaging system. Optimization methods utilized to improve the antenna perfomance are discussed. The presented transimpedance amplifier design offers a low noise figure and a protection for the diode, as it regulates the diode voltage to zero. An optimal diode impedance for this amplifier topology is derived. Simulation and measurement results are presented. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.broadb

Broadband Electrical Design and Modelling of Packages Integrated in LTCC-Substrate - Nisznansky, Martin; Ziegler, Christof; Schmidt, Lorenz-Peter; Hocke, Ralf; Wohlgemuth, O. (Proceedings of IMAPS Conference and Exhibition on Ceramic Interconnect Technology, 2003)
Substrate integrated package based on LTCC-technology with bandwidth of 50 GHz was designed. Full wave electromagnetic analysis of all included interconnects was performed and verified by measurement. Our work is especially focused on novel interconnects like flip-chip and differential transmission lines which enable an increase of bandwidth of the components. For the design of high speed SiGe-chips which will be embedded in LTCC-packages and modules it is interesting to know the influence of wire-bonds and flip-chip interconnects on module performance. Therefore equivalent circuit models were developed for these two typical structures that can be used in chip design tools like CADENCE. The behavior of interconnects were investigated not only in frequency domain but in time domain as well. As digital signals are processed an estimation of their distortion in the time domain is needed. Hence eye-diagrams were calculated from simulated data. Important digital signal characteristics like eye-opening and jitter can be estimated from this diagram. From the presented results we can see that the designed interconnects for LTCC-packages fulfill the requirements on bandwidth and minimize signal distortion.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.broadb
Keywords: Circuit model; Coupled lines; Differential excitation; Flip-chip; High speed interconnects; Wire-bond

Broadband millimetre-wave PIN-diode attenuator with double-ridge waveguide flanges - Schmidt, Lorenz-Peter; Meinel, H (Electronics Letters, 1982)
lhft_intern.bib::Schmidt11

Broadband, nonuniform stripline directional couplers for use in VNA testsets - Hrobak, M.; Sterns, M.; Seler, E.; Schrauder, T.; Schramm, M.; Schmidt, Lorenz-Peter (7th German Microwave Conference (GeMiC2012), 2012)
Scattering parameter testsets of vector network analyzer (VNA) base instruments require backward wave directional couplers with sufficiently high directivity. This paper describes a synthesis procedure of symmetric, nonuniform couplers based on common multilayer printed circuit board (PCB) technology. The utilized offset coupled striplines (STL) are characterized by 2D electromagnetic (EM) field simulations in the frequency domain. Two loose directional couplers with directivity values greater than 15 dB from 0.003 MHz to 40 GHz resp. 29 GHz and greater than 5 dB up to 50 GHz resp. 70 GHz are proposed. The necessity of well matched transitions from STL to microstrip line (MSL) is outlined and two possible realizations are discussed. Measurement data of the manufactured couplers is presented, the arising deviations are clearly mapped to specific manufacturing tolerances. The minimum requirements for the applied PCB technology that guarantee successful designs are highlighted.
lhft_intern.bib::hrobakGemicCoup

Broadband Planar Ring Mixers with DGS-Marchand Baluns in the Millimeter Wave Frequency Range - Rehner, Robert; Schneiderbanger, Dirk; Sterns, Michael; Martius, Siegfried; Schmidt, Lorenz-Peter (GEMIC March 2008, 2008)
Planar hybrid ring mixers in the millimeter wave range for frequencies up to 80 GHz are presented. They exhibit conversion losses lower than 15 dB up to frequencies higher than 70 GHz, with a very wide IF-bandwidth range from DC up to 22 GHz. The balancing of the input signals is realized by using broadband DGS-Marchand baluns, thus enabling an operation bandwidth of the mixers of more than 80%. The very high couplings at the baluns are realized by applying defected ground structures to the backside metallization of the circuits. The mixer circuits can be easily integrated into larger circuits. The design and the measurement results for three different mixer realizations are presented and compared.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.broadb

Broadband polarimetric mmWave antennas with differential stripline feed - Thurn, Karsten; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (European Conference on Antennas and Propagation, 2012)
Two approaches for differentially fed, polarimetric antennas with a center frequency of 77.5 GHz are introduced. These are an aperture-coupled patch (ACP) antenna and a monopole antenna with two differentially fed monopole pairs. Easy planar integration with differential MMICs is given through the differential stripline feed. Both antennas are designed for high bandwidth from 70 to 85 GHz for 10 dB return loss and high polarization purity. A stacked conical horn included in both designs results in a high gain of 8.5 dBi and a radiation pattern with one symmetric main beam without significant side lobes, reducing coupling to other elements in a future antenna array. After an introduction, design goals for the antennas are presented. Then, the design procedures for the two concepts are described together with simulation results. For measurement of the antennas, a feed network has been developed and the monopole antenna has been chosen for realization. The paper will be concluded by measurement results that are in good agreement with the simulations.
lhft_intern.bib::Thurn2012

Calibration of electromagnetic field simulations of MR coil arraysfor accurate quantitative comparison with the measured image SNR - Stumpf, C.; Rehner, R.; Martius, Siegfried; Vester, M.; Engelbrecht, Rainer; Schmidt, Lorenz-Peter (Intl. Soc. Mag. Reson. Med. 20th, 2012)
lhft_intern.bib::Stumpf2012

Cavity Damping of a 2.5 THz Resonator System Using Electro-Optically Stimulated Silicon - Biber, Stephan; Schneiderbanger, Dirk; Schulz, R.; Schmidt, Lorenz-Peter (Proceedings of the 28th Int. Conference on Infrared and Milimeter Waves, Otsu, Japan, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.cavity

Characteristics of a generalized fin-line for millimeter wave integrated circuits - Schmidt, Lorenz-Peter; Itoh, T (International Journal of Infrared and Millimeter Waves, 1981)
Generalized fin-lines are analyzed which consist of slots located on more than one interface between dielectric layers inserted in parallel with the E-plane of a waveguide. The analysis is based on a simplified formulation technique based on the spectral domain immittance matrix followed by a Galerkin's method. It allows as many slots as one desires at each interface, and the locations and the widths of these slots are arbitrary. The numerical process to carry out the present analysis is rather efficient. Some numerical data, including propagation constants of the propagating modes as well as characteristic impedances are presented for several structures considered useful for millimeter-wave circuit application
lhft_intern.bib::Schmidt5

Characteristics of Unilateral Fin-Line Structures with Arbitrarily Located Slots - Schmidt, Lorenz-Peter; Itoh, T; Hofmann, H (MTT-Symposium and IEEE Trans. MTT-29, 1980)
Generalized unilateral fin-line configurations for extended mm-wave applications are analyzed using the equivalent transmission line concept in the spectral domain. Numerical results for the frequency dependent propagation constants and characteristic impedances of various structures are presente
lhft_intern.bib::Schmidt6

Characterization of Micromachined Waveguide Hybrids at 350 and 650 GHz - Biber, Stephan; Murk, A.; Tils, T.; Pütz, P.; Schmidt, Lorenz-Peter; Kämpfer, N. (17th International Symposium on Space THz Technology - ISSTT 2006, Paris, May, 2006)
We present measurement results of two different hybrid couplers at submillimeter wavelengths. The devices under test were a 650 GHz coupler, which has been micromachined in Silicon by deep reactive ion etching, and two versions of a 345 GHz coupler machined out of brass. In order to determine the amplitude and phase balance of the coupling section the differences between the connecting waveguides have to be taken into account. We corrected the measurements under the assumption that the coupling section itself is fully symmetrical, which results in a good matching between the measured and the simulated performance.
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.charac

Collaborative Research Centre 694 “Integration of electronic components into mobile systems”–Motivation and survey - Weckenmann, Albert; Schmidt, Lorenz-Peter; Bookjans, M. (Science Direct, Physics Procedia 5, 2010)
lhft_intern.bib::Schmidt2010

Commercial applications of mm-waves (invited paper) - Schmidt, Lorenz-Peter (ESA Workshop on Millimeter Wave Technology and Applications, 1995)
lhft_intern.bib::Schmidt33

Comparative Noise Characterization and Conversion Loss Measurements of Schottky Diode Mixers at 600 GHz - Schür, Jan; Biber, Stephan; Cojocari, O.; Schmidt, Lorenz-Peter; Hartnagel, H. (30th Workshop on Compound Semiconductor Devices and Integrated Circuits, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.compar

Conformal Superstrate Loaded Automotive Radar Antenna for Integration in Polymer Car Body Panels - Kilian, Andreas; Schmidt, Lorenz-Peter (Antennas and Propagation (EuCAP), 2010 Proceedings of the Fourth European Conference on, 2010)
In this contribution the design process for hot embossed millimeter-wave antennas integrated in plastic multilayer car body panels is presented. Starting from material characteristics and fixed parameters obtained by the investigation of the fabrication process steps, the design of a microstrip patch antenna working at 24GHz will be demonstrated. The antenna is embedded within a plastic multi-layer structure by laminating the substrate layer with a paint foil and reinforcing the part by back injection molding. The comparison between simulation and measurement results will give information about the producibility of conformal integrated antennas for automotive radar applications like pre-crash detection or parking aid.
lhft_intern.bib::Kilian10a

Considerations for Future Automotive Radar in the Frequency Range Above 100 GHz - Köhler, Aaron; Gumbmann, Frank; Schür, Jan; Schmidt, Lorenz-Peter; Bloecher, H.-J. (RoCC-Session , GeMiC 2010, Berlin, 2010)
Within the last years automotive radar sensors became more and more important. Started with comfort systems like adaptive cruise control (ACC) and parking aid, the safety aspect increasingly came to the fore. In the near future not only upper class cars will be equipped with various radar applications like pre crash, collision warning and collision avoidance to increase traffic safety. Therefore many high performance radar sensors have to be integrated in the car. This paper describes the demands on future radar sensors. It is discussed how the step to higher operating frequencies could be beneficial particularly for urban situations with high traffic density. Furthermore the paper will provide and discuss design considerations for future mmW-Radar sensors in automotive safety applications.
lhft_intern.bib::Koehler10

Corrections to "Design and Fabrication of Broadband Hybrid GaAs Schottky Diode Frequency Multipliers" - Hrobak, Michael; Sterns, Michael; Schramm, Markus; Stein, Wadim; Schmidt, Lorenz-Peter (IEEE Transactions on Microwave Theory and Techniques, 2015)
The block diagram shown in Fig 33 of the above-named paper [ibid., vol. 61, no. 12, pp. 4442–4460, Dec. 2013] is incorrect. Instead of series resonators, it should contain parallel resonators. A corrected version is provided here as Fig. 1. In the continuous text of the above paper [p. 4451, col. 2, line 38] it reads "MSL half-wave series resonator," which is incorrect. It should read "half-wave MSL parallel resonator
lhft_intern.bib::Hrobak2015

Cross-Polarized Imaging of Glass-Fibre Reinforced Plastics at mm-Waves - Nezadal, Martin; Schür, Jan; Schmidt, Lorenz-Peter (8th German Microwave Conference (GeMiC2014), 2014)
The non-destructive testing of compound materials, especially glass-fibre reinforced plastics (GFRP) with millimetrewaves looks very promising. This paper investigates an imaging system which evaluates the cross-polarized signal in the W-Band from 75 to 110 GHz with a synthetic aperture radar. As anomalies reflect the incoming signal in the parallel and orthogonal polarization, it has some advantages for defect detection. It was possible to locate all defects in the measured samples even in depths of up to 14.5mm in GFRP with diameters of down to 5 mm.
lhft_intern.bib::Nezadal2014

Current limited superconducting RF coils - Stumpf, Christopher; Frank, Tobias; Vester, Markus; Martius, Siegfried; Rehner, Robert; Engelbrecht, Rainer; Schmidt, Lorenz-Peter (Intl. Soc. Mag. Reson. Med. 22th, 2014)
lhft_intern.bib::Stumpf2014

Data Statistics and Image Properties of a Large Multistatic mm-Wave Imaging System - Schießl, Andreas; Ahmed, S. S.; Schmidt, Lorenz-Peter (14th International Radar Symposium IRS2013, 2013)
Near field radar systems offer potential solutions for security and non-destructive testing appplications. This work presents the system architecture of a fully electronic multistatic mm-wave imager at E-band. The measurement and processing chain of the imaging system is reviewed along with the corresponding data statistics. Reconstructed data of a complex test pattern with specific 3D elements is used to demonstrate the high imaging performance of the system. © 2013 German Inst of Navigation.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.datast

DC- and IF-noise performance optimization of GaAs Schottky diodes for THz applications - Cojocari, O.; Biber, Stephan; Mottet, B.; Rodriguez-Girones, M.; Hartnagel, H.; Schmidt, Lorenz-Peter (Semiconductor Science and Technology, 2005)
This paper presents results which originated from a long-term systematic optimization of surface processing prior to anode formation of THz Schottky-based components. Particularly, four most promising surface-processing approaches are carefully investigated separately and in combination in order to understand the chemical and physical processes occurring on a GaAs surface. A reliable technological approach for anode formation is identified, which exhibits optimal diode characteristics and production repeatability. A model is proposed for the influence of each process on the subsequent one in the fabrication process sequence. DC- and IF-noise measurements are performed using an automated measurement system providing statistically significant data. Very good de-parameters such as a series resistance of Rs = 15 ω, an ideality factor N = 1.168, a reverse current Is = 0.024 fA and an IF-noise temperature of 257 K at 1 mA current bias with a good uniformity are achieved for non-cooled Schottky diodes with an anode diameter of 1 μm. The best noise figure is measured to be as low as 220 K at 3.8 GHz and 1 mA current bias.
UnivIS-Import:2015-03-09:Pub.2005.tech.IE.LEH.dcandi

Design and construction of an ultrawideband backward wave directional coupler - Hrobak, Michael; Sterns, M.; Seler, Ernst; Schramm, Marcus; Schmidt, Lorenz-Peter (IET Microwaves Antennas & Propagation, 2012)
In this study the design and construction of an ultrawideband backward wave directional coupler is presented. The symmetric, non-uniform coupler covers the frequency range from 2 to 50 GHz with an average coupling of 16.6 2.4 dB while establishing directivity values greater than 10 dB from 10 MHz to 33.8 GHz and 8 dB up to 48.4 GHz. The design is based on coupled microstrip lines suitable for integration into planar front end modules of modern measurement systems. To account for the dispersive behaviour of such waveguides, wiggly-line technique is utilised. Accurate extraction of the waveguide frequency-dependent distributed equivalent circuit parameters is done by 2D finite element electromagnetic field (EM) simulation. To balance out the remaining mistuning appropriate scaling parameters are introduced. The influence of common manufacturing and assembly tolerances on the device performance is analysed. Measurement results of the synthesised coupler with planar matched isolated port are presente
lhft_intern.bib::hrobakIetCoup

Design and Experimental Verification of Correction Algorithms for Improving the Measurement Accuracy of a Broadband Vector IF Receiver at 160 MHz - Hofmann, A.; Kalb, A.; Manglberger, M.; Weinzierl, Jochen; Schmidt, Lorenz-Peter (Frequenz, Mai / Juni, 2005)
An Intermediate Frequency (IF) receiver unit with a center frequency of 160 MHz and a bandwidth of 80 MHz was recently developed as a core component of a novel heterodyne vector field measurement system at 150 GHz, 300 GHz and 450 GHz. The influence of different errors types on the measurement accuracy is systematically analyzed. Based on this, a strategy of enhancing the overall accuracy of the IF receiver by software algorithms was developed. Its effectiveness is verified by experimental characterization.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.design_4
Keywords: Accuracy enhancement; Correction algorithms; Iq demodulation; Thz measurements; Vector receiver

Design and Fabrication of Broadband Hybrid GaAs Schottky Diode Frequency Multipliers - Hrobak, Michael; Sterns, Michael; Schramm, Marcus; Stein, Wadim; Schmidt, Lorenz-Peter (IEEE Transactions on Microwave Theory and Techniques, 2013)
Frequency extender modules of vector network analyzers and signal generators, as well as front-end modules of semiconductor automatic test systems, make use of broadband resistive diode frequency multipliers. This paper presents the design and fabrication of innovative planar varistor frequency multipliers. Three frequency triplers (#1, #2, #3) and two frequency doublers (#4, #5), operating in the 60-110 GHz and 50-110 GHz frequency ranges, respectively, are designed. The hybrid architecture utilizes commercial gallium arsenide Schottky diodes from United Monolithic Semiconductors on thin-film processed high-permittivity alumina substrate. Synthesis is based on a co-simulation procedure between 3-D electromagnetic field and nonlinear harmonic balance circuit simulations. Scalar and spectral measurement data over the focused output frequency ranges are presented. Conversion loss values around 18 dB from 60 to 95 GHz and below 22 dB from 60 to 110 GHz are achieved with frequency tripler #1. Frequency doubler #5 achieves conversion loss values below 15 dB from 50 to 89 GHz and below 22 dB from 50 to 110 GHz. A comprehensive comparison of the presented work with reported frequency multipliers is included. © 2013 IEE
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.LEH.design
Keywords: 1.00-mm coaxial connector; Hybrid multiplier; Longitudinal E-field probe; Planar W -band multiplier; Schottky diode frequency multiplier; Varistor doubler; Varistor tripler

Design and Measurement of a Bandpass Filter at 300 GHz Based on a Highly Efficient Binary Grating - Biber, Stephan; Hofmann, Arnd; Schulz, R; Collischon, M; Weinzierl, Jochen; Schmidt, Lorenz-Peter (IEEE Transactions on Microwave Theory and Techniques, 2004)
A bandpass filter for 300 GHz with a stopband at 450 GHz based on a highly efficient binary grating as a frequency-selective element was developed and optimized. The geometry of the grating was carefully designed for a maximum difference angle between reflected beams at 300 and 450 GHz and for maximum efficiency at 300 GHz. The grating efficiency was optimized using a rigorous theory of diffraction, yielding a maximum efficiency of over 99.5% neglecting conductor losses. Antennas and elliptical mirrors are used for optimum quasi-optical illumination of the grating and Gaussian beam shaping. After an optimization and a comprehensive examination of the grating in an experimental heterodyne measurement setup at 300 GHz, the filter was implemented fixed tuned into a small housing with waveguide flanges. The fixed tuned setup with corrugated feed horns results in an overall flange-to-flange insertion loss of only 2.8 d
lhft_intern.bib::biber04b

Design and Measurement of a Wideband Aperture-Coupled and Polarization-Agile Stacked-Patch Antenna-Array for Monopulse Radar Applications - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (European Conference on Antennas and Propagation EuCAP, Berlin, March, 2009)
A wideband, circularly-polarized antenna array covering the frequency range 1.7 GHz to 2.5 GHz for telemetric monitoring and monopulse application is presented. Using a subarray design, monopulse functionality can be achieved with an external comparator network. The high bandwidth of 38 % is realized by using the principle of the aperture-coupled stacked-patch microstrip antenna. By integrating a quadrature coupler, the polarization sense can be selected. Sequential rotation technique is used for enhancing polarization purity. The theoretical analysis is based on the finite-difference time-domain (FDTD) method. A stacked-patch antenna element, a 2×2 antenna quadrant and a 4x4 antenna array have been designed, fabricated and measured. The measured return loss of one quadrant is better than 11 dB in the desired bandwidth for both circular polarization senses. Maximum antenna gain ranges between 7 dB and 18 dB for the sum pattern while the null depth of the difference pattern is always better than 30 dB. Theoretical and measured results of S parameters and radiation patterns are presented and discussed.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.design_7

Design and Measurements of Frequency Selective Surfaces on Silicon Substrates for Sub-mm Wave Applications - Biber, Stephan; Bozzi, M.; Perregrini, L.; Schmidt, Lorenz-Peter (ACES Conference of the Applied Computational Electromagnetic Society, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.design_7

Design and Testing of Frequency-Selective Surfaces on Silicon Substrates for Submillimeter-Wave Applications - Biber, Stephan; Bozzi, M.; Günther, O.; Perregrini, L.; Schmidt, Lorenz-Peter (IEEE Transactions on Antennas and Propagation, 2006)
A new class of frequency-selective surfaces (FSSs), to be used as quasi-optical filters for harmonic suppression in submillimeter-wave frequency multipliers, is proposed and experimentally verified. The FSSs consist of two-dimensional aperture arrays and are made from microstructured aluminum on electrically thick, high-resistivity silicon substrates. This leads to a very good mechanical stability, reasonably low insertion loss, and permits manufacture of the structure by using standard processes available from the semiconductor industries. This paper presents the design, fabrication, and testing of two sets of prototypes, the former with a passband at 300 GHz and a stopband at 450 GHz and the latter with a passband at 600 GHz and a stopband at 750 GHz. For both frequency ranges, FSSs with rectangular slots and with dogbone-shaped holes have been designed by using the method of moments/boundary integral-resonant mode expansion method. The effect of ohmic and dielectric losses has been determined by using the commercial code HFSS. Several prototypes have been fabricated, and measured by terahertz time-domain spectroscopy and continuous wave measurements, showing high reproducibility of the machining process, insertion loss between 1.0 and 1.6 dB, and stopband attenuation larger than 30 dB. Finally, we demonstrate that the incidence angle can be used as a degree of freedom for fine tuning the stopband, without practically changing the frequency response in the passband. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.LEH.design
Keywords: Frequency multipliers; Frequency-selective surfaces; Quasi-optics; Silicon; Submillimeter-wave technology

Design and Testing of Frequency Selective Surfaces on Thick Silicon Substrate Operating at 600 GHz - Biber, Stephan; Bozzi, M.; Günther, O.; Perregrini, L.; Schmidt, Lorenz-Peter (European Microwave Week, Paris, France, September, 2005)
This paper describes the design and experimental verification of frequency selective surfaces, to be used as quasi-optical niters in the sub-millimeter wave range. They consist of a thin metal layer perforated periodically with rectangular or dogbone-shaped holes, and supported by a thick silicon substrate. A set of filters with pass-band at 600 GHz and stop-band at 750 GHz have been designed and tested. The design procedure based on the MoM/BI-RME method, the manufacturing of prototypes by standard processes available from the semiconductor industries, and their measurement by CW and THz time-domain spectroscopy are reported in this work. This class of filters is mechanically robust, presents low losses (1.4 dB), exhibits good reproducibility, and permits a fine tuning of the stop-band frequency by slightly changing the incidence angle.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.design

Design considerations for a fixed tuned 300 GHz Heterostructure Barrier Charge Swing tripler - Ruf, Marcel; Schür, Jan; Bogdan, N.; Schmidt, Lorenz-Peter; Hartnagel, H. (Proceedings of the 3rd German Microwave Conference, 2008)
A simulative investigation of a microstrip-based environment for a planar Heterostructure Barrier Charge Swing multiplier optimized for tripler operation from 100 GHz to 300 GHz is presented. Design considerations for both the planar circuitry and the geometrical dimensions of the split-block mount are given. Results obtained by full 3D electromagnetic software simulations are presented and experimentally validated by transmission measurements of scaled models of antipodal finline tapers in W-band frequency range.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.design

Design considerations for the hot embossing of microstrip antennas on plastic foils - Kilian, Andreas; Fuchs, Manuel; Schmidt, Lorenz-Peter (International Journal of Microwave and Wireless Technologies, 2009)
In this contribution, fundamental design considerations for a novel metallization technique to realize millimeter-wave microstrip structures are presented. This hot embossing technology is a fast and economic process originating from the production of three-dimensional molded interconnect devices. Conductive structures are coated onto plastic parts or plastic foils using a heated stamp. This approach shows high potential and therefore will be investigated for the fabrication of low-cost printed antennas at millimeter-wave frequencies. The focus of this contribution is on design guidelines considering process parameters and interactions with substrate and copper foil characteristics derived from the fabrication and measurement of single microstrip patch antenna prototypes for radar applications in the industrial, scientific and medical (ISM) band at 24GHz. Far-reaching potential lies in the utilization of the three-dimensional manufacturing technology for the construction of conformal integrated antenna systems based on the thermoforming capabilities of polymer substrates. © 2009 Cambridge University Press and the European Microwave Association.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.LEH.design
Keywords: Hot embossing; Low-cost fabrication; Metallization technique; Microstrip patch antenna; Molded interconnect devices

Design of a 4th Harmonic Schottky Diode Mixer for THz Frequencies - Schür, Jan; Ruf, Marcel; Schmidt, Lorenz-Peter (32th International Conference on Infrared and Millimeter Waves, 2007)
This paper focuses on the benefits of subharmonic mixers in the sub-mm wavelength range. To demonstrate the possibility to extend the advantages of 2nd harmonic mixers with respect to local oscillator requirements the paper discusses higher order subharmonic mixers. Simulation results are presented to show the achievable performance and limitations of higher order subharmonical mixing. For an exemplary 4th harmonic mixer operating at 600 GHz the circuit simulations predict a conversion loss of around 15 dB. Results of 3D-EM field simulations are presented to demonstrate a very compact split-block realization of the mixer circuitry.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.design
Keywords: 4th harmonic; 600 GHz; GaAs Schottky diode; Mixer; THz

Design of a Balanced-Fed Patch-Excited Horn Antenna at Millimeter-Wave Frequencies - Methfessel, S.; Schmidt, Lorenz-Peter (European Conference on Antennas and Propagation, EuCAP 2010, Barcelona, Spain, April, 2010)
In this paper, a patch-excited horn antenna with a center frequency of 79 GHz is introduced. Its plane of polarization can be rotated by 45° relative to the balanced feed, which is useful for multi-element array radar applications with digital beam forming (DBF) capabilities, where easy planar integration with transceiver chips is essential. The stacked conical horn is responsible for the high gain radiation pattern while maintaining the planar nature of the patch element. The non rotated but matched antenna has a measured gain of more than 8 dBi in boresight direction, while the sideway radiation is always 20 dB lower than the main beam, reducing mutual coupling and crosstalk. Radiation characteristics are enhanced with a substrate integrated cavity. This design achieves a relative bandwidth of 18 % by using an aperture coupled patch element. Simulation and measurement are in good agreement. After an introduction, the design of three antenna variants is presented, including some simulation results. The paper will be concluded by the measurement setup and measurements of the radiation pattern and return loss.
lhft_intern.bib::Methfessel10

Design of a Controllable Attenuator with High Dynamic Range for THz-Frequencies based on Optically Stimulated Free Carriers in High-Resistivity Silicon - Biber, Stephan; Schneiderbanger, Dirk; Schmidt, Lorenz-Peter (Frequenz, June, 2005)
As the variety of passive circuit components for the 0.3-5 THz domain is rarely developed, we examine the possibilities to use electro-optically stimulated high resistivity float-zone silicon for the design of a tunable attenuator for quasi-optical systems operating at 580 GHz. Possible applications also include switches and modulators for millimeter and submillimeter-waves. A fiber-coupled 1W CW near infrared (MIR) diode-laser is used to illuminate a silicon slab and creates electron-hole pairs in the bulk silicon. At the operating frequency, the silicon slab acts as a Fabry-Perot resonator to minimize insertion loss due to unwanted reflections from the air-silicon interface. A second silicon slab with micromachined anti-reflection coating is used to shield the NIR to ensure safe operation. We achieve more than 35 dB dynamic range with an insertion loss of less than 0.5 dB.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.design_3
Keywords: Electro-optical effects in silicon; Quasioptics; THz-technology; Variable attenuator

Design of Artificial Dielectrics for Anti-Reflection-Coatings - Biber, Stephan; Martius, Siegfried; Schmidt, Lorenz-Peter; et al. (Proceedings of the 33rd European Microwave Conference, 2003)
With the increasing interest in new artificial materials ranging from meta-materials to photonic bandgap materials there is a growing need for accurate models of artificial materials. We examine the design of a three-layer structure with an artificial dielectric as an anti-reflection-coating on both sides of a dielectric slab. We present a field-equivalent circuit theory to calculate the effective dielectric constant of the structured dielectric. The materials discussed in this paper have a lateral periodicity smaller than λ/10 and can easily be manufactured from high density polyethylene (HDPE) for frequencies up to 20 GHz. The field-analog circuit theory can also be used to calculate the polarization dependence of the artificial dielectric. Theoretical results of three geometrically different structures were compared with waveguide measurements at X-band and showed excellent agreement. Applications such as the design of new components at millimeter and submillimeter wave frequencies are discussed, considering the X-Band measurements as a scaled model. © 2003 EUMA.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.design

Design of New Passive THz Devices based on Micromachining Techniques - Biber, Stephan; Schür, Jan; Hofmann, Arnd; Schmidt, Lorenz-Peter (Proc. of Kharkov Symposium on Physics and Engineering of Microwaves, Millimeter and Submillimeter Waves, Kharkov, Ukraine, June, 2004)
We present an overview on the latest results using micromachining techniques far the fabrication of THz-components. Different machining techniques will be discussed with respect to their capability to generate complex 3-dimensional geometries with high aspect ratios and to meet the high mechanical requirements for THz-components. Exemplary results for the application of micromachining techniques for the design of new components will be reviewed. We will emphasize the potential of silicon based microstructures for the manufacturing of new devices.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.design_4

Design of Sparse MIMO Arrays for Short Range Imaging Applications - Gumbmann, F.; Schmidt, Lorenz-Peter (Asia-Pacific Microwave Conference (APMC) 2010, 2010)
This paper presents the development of a sparse periodic array for short range imaging applications in the frequency range 75–90 GHz. The basis for the array design is the effective aperture approach, which is a farfield design procedure. For short target distances and a wide field of view the result of this concept is not satisfying. An extension of the sparse periodic array concept for short range applications on the basis of an optimized array design and an optimized beamforming algorithm is presented in this wor
lhft_intern.bib::Gumbmann10

Detection of SSR Signals in Multipath Airport Environments by a Multichannel Receiver - Reck, C.; Berold, U.; Schmidt, Lorenz-Peter (Asia Pacific Microwave Conference, Yokohama, Japan, December, 2010)
Multipath propagation is a serious problem with Secondary Surveillance Radar (SSR) systems at airport apron and taxiway areas. In this approach, effective suppression of interference (garbling) by multipath components, using a multichannel receiver is presented. Thereby the SSR header format is exploited to detect multipath components, which are then eliminated by subspace based signal suppression. Extensive tests at Frankfurt international airport show the potential of the proposed approach to significantly improve reception at problematic sites.
lhft_intern.bib::Reck10b

Die Kunststoffkarroserie als Träger mehrlagiger, konformer Folienantennen fuer Automobilradarsysteme - Kilian, Andreas; Schmidt, Lorenz-Peter (WSAA, 2010)
lhft_intern.bib::Kilian10b

Dielectric Data of Ceramic Substrates at High Frequencies - Stiegelschmitt, Alfons; Roosen, Andreas; Ziegler, Christof; Martius, Siegfried; Schmidt, Lorenz-Peter (Journal of the European Ceramic Society, 2004)
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.LEH.dielec

Dielectric Rod Antennas as Optimized Feed Elements for Focal Plane Arrays, Washington - Richter, Jürgen; Schmidt, Lorenz-Peter (Proceedings of the IEEE International Antennas and Propagation Symposium 2005, Washington, D.C.,July, 2005)
Dielectric rod antennas of rectangular cross section have a number of significant advantages over conventional waveguide or horn antennas when used as feed elements in focal plane arrays. They provide a broadband input matching, a much lower mutual coupling and an appreciable reduction of spillover losses even in densely packed feed arrays. The design, simulation, optimization and experimental investigation of feed arrays with waveguide- and slotline-fed dielectric rod antennas at millimeter-wave frequencies is presented.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.dielec

Dielectric Rod Waveguide Couplers as Harmonic Filters for Millimeter and Sub-Millimeter Wave Frequencies - Hofmann, A.; Manglberger, M.; Biber, Stephan; Weinzierl, Jochen; Schmidt, Lorenz-Peter; Brand, Hans (GeMiC 2006, Karlsruhe, April, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.dielec

Dielectric Wide Angle Lenses for Millimeter-Wave Focal Plane Imaging - Richter, Jürgen; Hofmann, Arnd; Schmidt, Lorenz-Peter (Proceedings of the 31st European Microwave Conference, 2001)
Various design procedures for millimeter-wave dielectric lenses have been studied and compared with regard to the wide angle characteristics of the resulting lens contours. The paper describes the simulation and optimisation of the focusing properties of the lenses for large scanning angles using a hybrid method involving ray-tracing techniques and aperture field integration, the realisation of unzoned and zoned lenses and the farfield pattern measurements at 75 and 150 GHz. The theoretical and experimental results show that a scanning range of 40° (±20°) with very low beam degradation can be achieved. © 2001 IEEE.
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.dielec

Differential Excitation of a Hybrid Antenna for a 75 GHz Antenna Array Implemented on a Multilayer PC Board - Juenemann, R.; Zielska, A.; Schießl, Andreas; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
If, for practical reasons, there is a need to bend a differential waveguide, the bend has to be compensated to avoid mode conversion into the common mode which can lead to unwanted resonance effects. This paper deals with two possible compensating structures for a 45° bend in a differential waveguide exciting a hybrid antenna. The hybrid antenna in turn is part of a large array used in a security scanner for people screening. Simulations show antenna behavior with and without compensation with respect to matching, mode conversion, gain, and suppression of the cross polarization. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.differ
Keywords: antenna feed; differential amplifier; horn antenna; microwave imaging; mode conversion

Direction of Arrival Estimation from Secondary Surveillance RadarSignals in Presence of Hardware Imperfections - Reck, C; Berold, Ulrich; Weinzierl, Jochen; Schmidt, Lorenz-Peter (European Microwave Week / EuRAD, Amsterdam, October, 2008)
lhft_intern.bib::Reck08

Direction of Arrival Sensor Calibration based on ADS-B Airborne Position Telegrams - Reck, Christoph; Berold, Ulrich; Schür, Jan; Schmidt, Lorenz-Peter (EuMW / EuRAD, Rom, September, 2009)
This paper investigates the suitability of ADS-B airborne position messages for calibrating a direction of arrival (DOA) sensor for Secondary Surveillance Radar (SSR) signals at runtime. An ad hoc system is thereby utilized to receive, automatically select and process a statistically relevant number of ADS-B replies. It is experimentally shown that ADS-B transponders can provide a suitable calibration signal within some limitations.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.direct

Ein Verfahren zur Ermittlung komplexer Dielektrizitätskonstantenduenner Folien im Millimeterwellenbereich - Schmidt, Lorenz-Peter; Hofmann, H (AEÜ - International Journal of Electronics and Communications, 1979)
lhft_intern.bib::Schmidt79

End face coupling as detachable connection of dielectric waveguides at 75 GHz and 300 GHz - Weinzierl, Jochen; Schmidt, Lorenz-Peter; Hörster, Eva; et al. (Conference Digest of the 2004 Joint 29th International Conference on Infrared and Millimeter Waves and 12th International Conference on Terahertz Electronics, 2004)
End face coupling of rectangular dielectric waveguides at 75 GHz and 300 GHz is presented as a new, low-loss and powerful method for novel switching and multiplexing applications of MMW and SMMW signals. The coupling of the waveguides has been investigated, designed and optimized by extensive numerical field simulations and experimental verification at both frequencies. © 2004 IEEE.

Estimation of frequency conversion efficiency of THz devices using a ballistic electron wave swing circuit model - Schildbach, Christian; Ong, Duu Sheng; Hartnagel, Hans; Schmidt, Lorenz-Peter (Semiconductor Science and Technology, 2016)
The ballistic electron wave swing device has previously been presented as a possible candidate for a simple power conversion technique to the THz -domain. This paper gives a simulative estimation of the power conversion efficiency. The harmonic balance simulations use an equivalent circuit model, which is also derived in this work from a mechanical model. To verify the validity of the circuit model, current waveforms are compared to Monte Carlo simulations of identical setups. Model parameters are given for a wide range of device configurations. The device configuration exhibiting the most conforming waveform is used further for determining the best conversion efficiency. The corresponding simulation setup is described. Simulation results implying a conversion efficiency of about 22% are presente
lhft_intern.bib::Schildbach2016

Experimental Characterization of a Wide Angle Lens for Millimeter-Wave Imaging - Richter, Jürgen; Simon, Alexander; Schmidt, Lorenz-Peter (Proc. of the IEEE International Antennas and Propagation Symposium, Washington D.C., July, 2005)
The field of view of wide angle dielectric lens antennas for focal plane arrays is mainly limited due to astigmatic aberrations which are often not taken into consideration even in more complex coma-corrected lens designs with two aspheric surfaces. This paper describes an efficient compact range setup for the measurement of high-gain lens antennas in small antenna chambers and presents a thorough experimental study of the effects of astigmatism and feed displacement/misalignment on the pattern degradation for large scanning angles. An experimentally derived method to minimize these aberrations is explained, resulting in a fairly constant beam quality with a maximized gain over a large field of view of 40°. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.experi_7

Experimental Characterization of a Wide Angle Lens for Millimeter-WaveImaging, Washington, DC, USA, July - Richter, J; Simon, A; Schmidt, Lorenz-Peter (APS-Symposium, Washington, DC, USA, July, 2005)
lhft_intern.bib::richter05

Experimental Phase Center Determination of Millimeterwave Antennas using Scaled Models at X-Band Frequencies - Richter, Jürgen; Biber, Stephan; Schmidt, Lorenz-Peter; Simon, J. (AMTA Europe Symposium Munich, May, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.experi_8

Experimental Verification of Particle-in-cell Simulation Results concerning Capacitive Pickup Devices - Ruf, Marcel; Schmidt, Lorenz-Peter; Setzer, St. (Proceedings of DIPAC09, 2009)
For beam position monitoring purposes, three different approaches have been applied to investigate and compare pickup button and electron beam spectrum characteristics. Results on this simulative approach are presented. Induced pickup currents have been calculated both with an analytical and a numerical method. An experimental validation of these simulation results has been conducted with the 6-MeV electron beam from a linear accelerator for medical purposes. The measurements were conducted under non-vacuum conditions. Good agreement between particle-in-cell simulation and experimental data was achieved concerning pickup power spectral distribution and dependence from beam current and beam displacements although non-negligible electron spread during air passage of the electron beam cannot be avoided.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.experi

Fast Multistatic Measurement System for Short Range Imaging Radar Development - Schießl, Andreas; Ahmed, S. S.; Genghammer, A.; Schmidt, Lorenz-Peter (12th URSI Commission-F Triennial Open Symposium on Radio Wave Propagation and Remote Sensing, 2011)
lhft_intern.bib::Schiessl11

Feasibility of Automotive Radar at Frequencies beyond 100 GHz - Köhler, Mike; Hasch, Juergen; Bloecher, Hans Ludwig; Schmidt, Lorenz-Peter (International Journal of Microwave and Wireless Technologies, 2012)
Radar sensors are used widely in modern driver assistance systems. Available sensors nowadays often operate in the 77 GHz band and can accurately provide distance, velocity, and angle information about remote objects. Increasing the operation frequency allows improving the angular resolution and accuracy. In this paper, the technical feasibility to move the operation frequency beyond 100 GHz is discussed, by investigating dielectric properties of radome materials, the attenuation of rain and atmosphere, radar cross-section behavior, active circuits technology, and frequency regulation issues. Moreover, a miniaturized antenna at 150 GHz is presented to demonstrate the possibilities of high-resolution radar for car
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.LEH.feasib

Feasibility of automotive radar at frequencies beyond 100 GHz - Köhler, Mike; Hasch, Juergen; Bloecher, Hans Ludwig; Schmidt, Lorenz-Peter (International Journal of Microwave and Wireless Technologies, 2013)
Radar sensors are used widely in modern driver assistance systems. Available sensors nowadays often operate in the 77 GHz band and can accurately provide distance, velocity, and angle information about remote objects. Increasing the operation frequency allows improving the angular resolution and accuracy. In this paper, the technical feasibility to move the operation frequency beyond 100 GHz is discussed, by investigating dielectric properties of radome materials, the attenuation of rain and atmosphere, radar cross-section behavior, active circuits technology, and frequency regulation issues. Moreover, a miniaturized antenna at 150 GHz is presented to demonstrate the possibilities of high-resolution radar for car
lhft_intern.bib::Koehler2012

Fin-line PIN-diode switches for mm-waves with extremely high isolationand short switching time - Callsen, H; Schmidt, Lorenz-Peter (ibid, 1987)
lhft_intern.bib::Schmidt16

Flexible low-loss dielectric waveguides for THz frequencies with transitions to metal waveguides - Hofmann, Arnd; Hörster, Eva; Weinzierl, Jochen; Schmidt, Lorenz-Peter; Brand, Hans (33rd European Microwave Conference, EuMC 2003, 2003)
A flexible low-loss dielectric waveguide system for sub-millimetre wave frequencies up to 600 GHz is presented, with measured attenuation values shown at 300 GHz. Mode transformers for an accurate and reproducible transition to metal waveguides have been investigated and improved. © 2003 EUMA.

FM-ICW monopulse radar sensor - Schmidt, Lorenz-Peter; Jester, R; Kadisch, G (Military Microwave Conference, 1990)
lhft_intern.bib::Schmidt20

Four-port on Wafer Measurement of Coupled Transmission Lines on LTCC - Ziegler, Christof; Nisznansky, Martin; Schmidt, Lorenz-Peter; Hocke, Ralf; Wohlgemuth, O. (Proceedings of IMAPS Conference and Exhibition on Ceramic Interconnect Technology, 2003)
The measurement results of coupled transmission lines on LTCC multilayer substrates are presented in this paper. The S-parameters of 4-port devices have been measured using a newly developed topology of a multiport vector network analyzer (VNA). A method for a multiport calibration based on multiple 2-port TRL-calibration routines is presented. The procedure has been developed for the use of a wafer probe station with coupled probe tips in combination with the 4-port VNA. To extract information about the capabilities of the measurement system, the measured data of the coupled microstrip lines on LTCC are compared to the results of a numerical circuit simulation of these lines. The measured single-ended S-parameters were transformed to a modal description by matrix transformation, describing the characteristics of the measured devices at common-mode or differential-mode stimulus. The results of the measurements and simulations will be discussed.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.fourpo
Keywords: Calibration; Modal S-parameters; Multiport; Network analysis; TRL

Frontend MMICs for millimeter wave frequencies up to 100 GHz - Adelseck, B; Schmidt, Lorenz-Peter; Dieudonne, J; Guettich, U; Klaassen, A; Coloquhoun, A (Military Microwave Conference, 1992)
lhft_intern.bib::Schmidt25

Full polarimetric THz imaging system in comparison with infraredthermography - Nezadal, Martin; Schür, Jan; Schmidt, Lorenz-Peter (11th European Conference on Non-Destructive Testing, 2014)
lhft_intern.bib::NezadalECNDT2014

Fully Electronic Active E-Band Personnel Imager with 2 m^2 Aperture - Ahmed, Sherif Sayed; Genghammer, Andreas; Schießl, Andreas; Schmidt, Lorenz-Peter (IEEE MTT-S International Microwave Symposium 2012 (IMS 2012), 2012)
The demand on advanced personnel screening systems led to the development of several active and passive imagers. Among them, active multistatic imaging ensures high image quality and allows fully electronic screening. An active E-band imager is introduced in this paper, which operates in real-time and delivers images of 30-dB dynamic range. Imaging of humans is achieved by optimizing the acquisition time using a dedicated digital signal processing solutio
lhft_intern.bib::Ahmed2012b

GaAs MMIC based components and frontends for millimeterwave communication and sensor systems - Dämbkes, H; Adelseck, B; Schmidt, Lorenz-Peter; Schroth, J (Microwave Systems Conference, 1995)
In the millimeter wave region several communication and sensor systems are emerging which presently are served only by III/V based technologies. First sensor systems of relevant volume market are tested at 76 GHz for automotive sensors, with other systems operating at 60 GHz and 94 GHz. For mm-wave communication systems volume applications arise at 38 GHz for the interconnection of PCN cells. This paper describes GaAs based technologies and components which are available to serve the requirements of mm-wave communication sensor systems up to 80 GH
lhft_intern.bib::Schmidt34

GaAs Schottky diode fabrication for THz-frequency mixer applications - Cojocari, O.; Biber, Stephan; Mottet, B.; Hartnagel, H.; Schmidt, Lorenz-Peter (Proc. the 28th Workshop on Compound Semiconductor Device and Integrated Circuits held in Europe, Smolenice Castle, Slovakia, 17-19 May, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.gaassc

Gas Discharge Impedance and Transmission Line Voltages in a RF Excited CO₂ Slab Laser - Engelbrecht, Rainer; Schulz, R.; Seibert, Günter; Hagen, J.; Schmidt, Lorenz-Peter (Frequenz, 2005)
The impedance of a RF excited gas discharge slab-type CO 2 laser is determined experimentally. The electrode pair is treated as a lossy transmission line to calculate the voltage distribution along the electrodes. Optimum inductances for homogenization of the gas discharge are derived and compared with experimental results.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.gasdis
Keywords: Carbon dioxide; Lasers; Lossy transmission line; RF gas discharge

Global navigation satellite systems in passive surveillance applications - Wachtl, Stefan; Koch, Volker; Schmidt, Lorenz-Peter (ESAV'14 - Enhanced Surveillance of Aircraft and Vehicles International Workshop, 2014)
The possibility to detect and analyze multipath signals of global navigation satellite systems (GNSS) caused by aircrafts is an attractive basis for the development of a passive surveillance sensor. Due to the fact that the received signal strength of global navigation satellite systems on earth surface is very low and the radar cross sections (RCS) of an aircraft strongly varies with the illumination and observation angles, such a passive sensor will offer a high probability of detection with respect to a hemispheric field of view preferably in a multistatic sensor array configuration. In this work measurements with a single sensor and considerations about possibilities to range an aircraft with a multistatic sensor array are presente
lhft_intern.bib::Wachtl2014

Grundlagen der Elektrotechnik 3 - Netzwerke, Foundations of Electrical Engineering 3 - Network Theory - Schmidt, Lorenz-Peter; Schaller, Gerhard; Martius, Siegfried (Pearson Education, Munich, Jan., 2006)
UnivIS-Import:2015-04-02:Pub.2006.tech.IE.LEH.grundl

Hardware Realization of a 2 m x 1 m Fully Electronic Real-Time mm-WaveImaging System - Schiessl, A.; Genghammer, A.; Ahmed, S. S.; Schmidt, Lorenz-Peter (EURSAR 2012, 2012)
A first generation of active mm-wave imaging devices is nowadays commercially available for industrial and security applications. Mostly, these systems use mechanical scanning to reduce channel count. The availability of state-of-the-art semiconductor technology enables reliably building high-channel-count fully electronic mm-wave imaging systems at E-Band frequencies, including parallel signal processing. Without the need for mechanical scanning, true real-time operation becomes possible. This work describes a prototype of such an imaging system for personnel screening applications. For the first time, hardware that is capable of capturing full 2 m × 1 m images of living persons in the 80 GHz region in real-time is demonstrated. An overview of the imaging system is given including detailed hardware description. The measurement flow is explained and the underlying link budget is derived.
lhft_intern.bib::Schiessl2012

Heterostructure Equivalence of Step-Recovery Diodes for Ballistic and Diffusive Electron Resonance - a New Concept for THz Signal Generation - Hartnagel, H.; Schmidt, Lorenz-Peter; Nicolae, B.; Oprea, I.; Schoenherr, D.; Ong, D.; Schür, Jan; Ruf, Marcel (Proceedings of 33rd international Conference on Infrared, Millimeter and Teherahertz Waves, 2008)
A heterostructure equivalent to the well-known step recovery diode principle, arranged as a double structure gives a new nonlinear device for highly efficient harmonic THz signal generation. Like in the case of step recovery diodes, these devices exhibit promising performance especially for the generation of higher order harmonics. Theoretical and experimental results will be presented. ©IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.hetero

High Precision DOA Estimation of SSR Transponder Signals - Reck, C.; Berold, U.; Schmidt, Lorenz-Peter (ICWITS, 2010)
lhft_intern.bib::Reck10a

High resolution permittivity reconstruction of one dimensional stratified dielectric media from broadband measurement data in the W-band - von Aschen, H.; Gumbmann, F.; Schmidt, Lorenz-Peter (Radar Conference (EuRAD), 2011 European, 2011)
For many security or Non Destructive Testing (NDT) applications it is desirable to detect and reconstruct dielectric stratified media to classify the investigated device under test (DUT). With rotational invariance techniques like the matrix pencil method (MPM) it is possible to improve the parameter estimation of a harmonic signal in contrast to the classical FFT based methods. By applying a time gating procedure prior to the MPM it is possible to reduce the influence of noise and multipath signals. Hence an improved parameter estimation is possible. Based on an optimized layer stripping algorithm it is possible to overestimate the number of layers in the stratified media and combine approximately similar layers.
lhft_intern.bib::aschen2011

High sensitivity millimeter-wave detectors using fin-line technology - Meinel, H; Schmidt, Lorenz-Peter (IR and mm-Waves, 1980)
lhft_intern.bib::Schmidt80a

Holographic Imaging Approach - Schildbach, C; Schmidt, Lorenz-Peter (Holographic Imaging Approach, 2017)
lhft_intern.bib::Schildbach2017

Homodyne Phase Sensitive Sub-millimetre Wave Transmission Measurements - Rehm, Guenther; Depser, J.; Schmidt, Lorenz-Peter (Proceedings of the 31st European Microwave Conference, 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.homody

Human biological monitoring - A versatile tool in the aftermath of a CBRN incident - Mueller, Michael; Schmiechen, Katharina; Heselmann, Deike; Schmidt, Lukas; Göen, Thomas; Schmidt, Lorenz-Peter (Toxicology Letters, 2014)
Human biological monitoring (HBM) is a well established tool in occupational and environmental medicine. It allows to determine the internal dose of a chemical absorbed by an individual after acute or chronic exposure. Biological reference and threshold values may be used to evaluate the internal dose and estimate its health impact(s). HBM and its advantages have not been broadly recognized from a civil protection point of view in Germany, therefore we have designed a compendium to define state-of-the-art HBM sampling after a release of chemicals in a civil protection scenario. The compendium integrates the sampling of biological agents and the sampling of radio-nuclear target isotopes, to be analyzed by HBM, in a single sampling approach, thus limiting burden on the potentially exposed persons and facilitating comparison of their individual exposure to different CBRN agents. HBM analysis methods are evaluated and basic toxicity data (including biological reference and threshold values) are given for a list of 50 agents, previously identified as relevant in civil protection. For on scene commanders and healthcare professionals the compendium may help to generate HBM and biological-radio-nuclear (BRN) exposure data after a CBRN incident which can be used to improve risk communication.
EVALuna2:9717

ICs fuer den Mikrowellenbereich; GaAs-Bausteine fuer vielfältige Anwendungen - Feldle, H; Schmidt, Lorenz-Peter; Narozny, P; Coloquhoun, A; Werres, C; Splettstoesser, J (Elektronik, 1991)
lhft_intern.bib::Schmidt23

IF-noise improvement of the GaAs Schottky diodes for THz-frequency mixer applications - Cojocari, O.; Biber, Stephan; Mottet, B.; Sydlo, C.; Hartnagel, H.; Schmidt, Lorenz-Peter (European Microwave Week 2003, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.ifnois

Illumination of humans in active millimeter-wave multistatic imaging - Ahmed, Sherif Sayed; Schmidt, Lorenz-Peter (European Conference on Antennas and Propagation (EUCAP), 2012)
The increasing demand on developing advanced imaging methods for the personnel screening applications has motivated many researchers to explore new techniques suitable to the emerging problem. Among the known methods, the active imaging using multistatic arrays in connection to digital-beamforming proofs efficient imaging with high image quality in terms of dynamic range and resolution. As any active imaging method, the illumination of the imaged object becomes an issue due to specular reflections. The human skin causes relatively strong specular reflections in the millimeter-wave range, and hence hinders the visibility of the body to some extend. Therefore, a consolidated understanding of the geometrical problem is essential for the optimization of the illumination issue. In this work, a simulation model is presented to address the problem precisely; and a measurement verification in the frequency range of 75 to 82 GHz is made to demonstrate the exactness of the proposed model. Additionally, an illumination analysis of a typical screening scenario of a human is presente
lhft_intern.bib::Ahmed2012

Illumination Properties of Multistatic Planar Arrays in Near-Field Imaging Applications - Ahmed, S. S.; Schiessl, A.; Schmidt, Lorenz-Peter (European Microwave Week, Paris, September, 2010)
The achievable illumination quality in microwave and millimeter-wave images using multistatic planar arrays is discussed. The geometrical relations between the array effective aperture and the illumination boundaries caused by the specular reflections are introduced. Afterwards, the variations in the processing gain due to diffuse and specular reflections are analyzed and verified experimentally.
lhft_intern.bib::Ahmed10

Imaging System for Non-Destructive Testing of Glass Fibre Reinforced Plastics - Nezadal, Martin; Schür, Jan; Schmidt, Lorenz-Peter (5th International Symposium on NDT in Aerospace, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.imagin

Impact Damage Analysis of Composite Materials With a mm-Wave Synthetic Aperture Radar - Nezadal, Martin; Schür, Jan; Schmidt, Lorenz-Peter (Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2013 38th International Conference on, 2013)
This paper presents investigations on impact damages on carbon and glass fibre reinforced plastics with a synthetic aperture radar in the frequency range of the W-Band (75 to 110 GHz) and J-Band (220 to 325 GHz). It was possible to detect the high energy impacts in the carbon fibre samples due to their phase delay in both bands. With the glass fibre samples it was also possible to detect changes in magnitude besides the phase delay. The three dimensional image reconstruction also revealed the damages beneath the surface. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.impact

Impact of Different Post-Processing Methods on a One-Receiver 2-Port Synthetic VNA Architecture - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter; Konrad, M. (European Microwave Conference, Proceedings, 2011)
Production test of RF and electronic circuits is mainly driven by two restrictions, the initial investment in the equipment and the required measurement time, mostly describing the overall cost of test. This is one reason for the increased interest in synthetic instrumentation. The measurement of complex scattering parameters using synthetic instruments has been demonstrated. Improvement of the measurement accuracy and the speed while preserving a cost efficient solution is the focus of this contribution. Comparing the hardware demands using different calibration and post-processing steps gives an insight into a cost efficient design of a synthetic Vector Network Analyzer (sVNA).
lhft_intern.bib::Schramm11a

Increasing Measurement Speed in mm-Wave Imaging Systems by Means of Frequency Multiplexing - Koeppel, Tobias; Methfessel, Sebastian Dirk; Schießl, Andreas; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Target movement during illumination causes reliability issues in imaging systems, particularly in applications where time efficiency is needed. A technique is proposed in order to reduce measurement time and as a consequence also motion blur effects. With the use of OFDM waveforms, a decrease in measurement time by a factor of 1.6 is achieved with minimal hardware costs. Measurement time for increasing numbers of carriers is predicted. A hardware realization is investigated with respect to hardware imperfections. Influence of intermodulation distortion and phase noise on dynamic range is discussed. Afterwards, imaging results are presented. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.increa
Keywords: microwave imaging; multistatic radar; signal processing; sparse array

Independent Surveillance Broadcast – ADS-B Receivers with DOA Estimation - Reck, Christoph; Reuther, M.; Jasch, A.; Schmidt, Lorenz-Peter (ESAV'11, 2011)
On the one hand air traffic control (ATC) institutions consider to use ADS-B for its low cost and simplicity of ground station hardware. Aircraft positions transmitted via ADS-B are on the other hand in some cases error prone. In the proposed approach, direction of arrival (DOA) estimation is used to verify ADS-B airborne positions. The potential positioning error of ADS-B is thereby evaluated by comparing DOA estimates to DOA calculated from ADS-B references. To proof the accuracy of the applied DOA estimation sensor, an additional measurement campaign using a dedicated measurement aircraft has been conducted.
lhft_intern.bib::Reck2011b

Inherent Resolution Limit Analysis for Millimeter-Wave Indirect Holographic Imaging - Adametz, Julian; Gumbmann, Frank; Schmidt, Lorenz-Peter (Frequenz, 2011)
In the classical indirect holographic setup, a wave emitted by the measurement object is superimposed with a reference wave at the aperture of the imaging system. The resulting interference pattern can be recorded with a simple intensity detection. However, the complex object field can be obtained from the plane wave spectrum (PWS) of the interference pattern. Dedicated methods can be used to calculate the field distribution at the object position, which is equivalent to the object properties and to an image of the object, respectively. This paper shows that the resolution of the created image is constricted due to the fact that the bandwidth of the extracted field is limited by the extraction process. A relation between the maximum possible bandwidth and the geometrical dimensions of the imager setup is deduced. Furthermore, a formula for the minimum achievable resolution is derived. Experimental results are presented to illustrate the issu
lhft_intern.bib::Adametz2014b

Integration and Performance Aspects of Automotive Radar at Millimeterwave and Sub-Millimeterwave Frequencies - Köhler, Aaron; Schür, Jan; Vossiek, Martin; Schmidt, Lorenz-Peter (IEEE MTT-S International Microwave Symposium 2015 (IMS 2015), 2015)
lhft_intern.bib::Koehler2015

Integration radarbasierter Fahrerassistenzsysteme in Kunststoffkarosserieteile - Fuchs, Michael; Drummer, Dietmar; Kilian, Andreas; Schmidt, Lorenz-Peter (Automotive meets Electronics, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEH.integr

Interconnects and Chip Modules for Broadband Digital Systems with Bitrates up to 80 GB/S - Nisznansky, Martin; Ziegler, Christof; Martius, Siegfried; Schmidt, Lorenz-Peter (13th Conference on Microwave Techniques, Prague, September 26-28, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.interc

Investigation of the hot embossing technology for low-cost antennas printed on polymer substrates - Kilian, Andreas; Weinzierl, Jochen; Schmidt, Lorenz-Peter (38th European Microwave Conference, EuMC 2008, 2008)
In this contribution a novel metallization technique for the realization of millimeter-wave microstrip patch antennas is presented. This technology called hot embossing is a fast and economic process originating from the production of threedimensional molded interconnect devices (3D-MID). Conductive structures are coated onto plastic parts or plastic foils using a heated stamp. To the best knowledge of the authors, this approach has not yet been employed and therefore will be investigated for the fabrication of low-cost printed antennas at millimeter-wave frequencies. The focus of this contribution is on the evaluation of process parameters and interactions with substrate and copper foil characteristics as well as the fabrication and measurement of single microstrip patch antennas designed for the 24 GHz ISM- band. Far-reaching potentials lie in the utilization of the threedimensional manufacturing technology for the construction of conformal integrated antennas. © 2008 EuMA.

Karosserieaussenhaut mit integrierter Antenne - Fuchs, Manuel; Kilian, Andreas; Brocka, Zaneta; Schmachtenberg, Ernst; Schmidt, Lorenz-Peter (Kunststoffe, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.LEH.kaross

Lineselective CO_2 Lasers with Anisotropic Etched Silicon Gratings - Schulz, R.; Hagen, J.; Schmidt, Lorenz-Peter (Conference on Lasers and Electrooptics 23.-27. 06.2003, München, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.linese

Lineselective CO_2-Lasers with Variable Line-Spacing and Variable Reflectivity Silicon Gratings - Schulz, R.; Collischon, M.; Brand, Hans; Schmidt, Lorenz-Peter (XV International Symposium on Gas Flow and Chemical Lasers, Prag, September, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.linese

Lineselective CO 2 -lasers with variable line-spacing and variable reflectivity silicon gratings - Schulz, R; Collischon, M; Brand, Hans; Schmidt, Lorenz-Peter (XV International Symposium on Gas Flow and Chemical Lasers, Prag, September, 2005)
A lineselective CO2-laser with an unstable resonator is presented. The CO2-laser is realised with an rf-excited slab geometry to get a compact design with high output power. As lineselective element a grating in Littrow mount is used. The gratings are manufactured by anisotropic etching of silicon. The grating has a variable duty cycle to obtain a variable reflectivity. Furthermore, gratings are presented that have focusing propteries by a variation of the grating periodicit
lhft_intern.bib::schulz04a

Low-Loss Frequency Selective Surfaces on Silicon Substrates for Sub-millimeter Wave Applications - Biber, Stephan; Bozzi, M.; Günther, O.; Perregrini, L.; Schmidt, Lorenz-Peter (Symposium on Antennas and Propagation, Washington DC, July, 2005)
A new class of frequency selective surfaces (FSSs), to be used as quasi-optical filters for harmonic suppression in sub-mm wave frequency multipliers, is proposed and experimentally verified. The FSSs consist of two-dimensional aperture arrays, and are made from microstructured aluminium on electrically thick, high-resistivity silicon substrates. This leads to a very good mechanical stability, low insertion loss, and permits to manufacture the structure by using standard processes available from the semiconductor industries. This paper presents the design, fabrication, and testing of two sets of prototypes, the former with a pass-band at 300 GHz and a stop-band at 450 GHz and the latter with a pass-band at 600 GHz and a stop-band at 750 GHz. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.lowlos

Low Loss Silicon Window Material for Submillimeter Waves Using Micromachined Artificial Dielectrics for Anti-Reflection Coating - Biber, Stephan; Schneiderbanger, Dirk; Schmidt, Lorenz-Peter (29th International Conference on Infrared and Millimeter Waves , September, 2004)
A high-resistivity silicon wafer was used to design a broad-band low loss window material for 600GHz by micromachining an artificial dielectric as a quarter wave transformer on the front and rear side of the wafer. The artificial dielectric is made from a 2-dimensional periodic structure to ensure the same transmission characteristics for horizontally and vertically polarized waves. © 2004 IEEE.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.lowlos

Magnetically Tunable Filter from 72 GHz to 95 GHz - Sterns, M.; Hrobak, M.; Martius, Siegfried; Schmidt, Lorenz-Peter (5th German Microwave Conference, 2010)
In this paper a magnetically tunable filter based on unilateral finlines is presented. The filter covers a tuning frequency range from 72 GHz to 95 GHz, achieving an insertion loss between 11.3 dB and 7.3 dB.
lhft_intern.bib::sterns10

Magnetically Tunable Hexaferrite Bandpass Filter from 43 GHz to 83.5 GHz - Sterns, Michael; Rehner, Robert; Schneiderbanger, Dirk; Martius, Siegfried; Schmidt, Lorenz-Peter (Proceedings of the 39th European Microwave Conference, 2009)
In this paper a novel magnetically tunable bandpass filter based on open-ended unilateral finlines is presented. The filter covers a tuning frequency range from 43 GHz to 83.5 GHz with a typical insertion loss between 6.7 dB and 8.5 dB. Hexaferrite resonators are used to obtain high resonant frequencies with comparatively low magnetic field strengths. Although only two resonators are used, an off resonance isolation of about 60 dB is achieved. In the cutoff region of the finlines the filter exhibits an off resonance isolation of more than 80 dB. The use of unilateral finlines as coupling lines simplifies the integration of the filter into a planar transmission line environment what is advantageous for the design of integrated high frequency modules. Further on, a considerably larger operating frequency range is covered, compared to classical rectangular waveguide based concepts.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.magnet

Mean and Differential Phase Centers of Rectangular Dielectric RodAntennas - Richter, J; Garbas, Jens-Uwe; Schmidt, Lorenz-Peter (2004)
lhft_intern.bib::richter04a

Mean and Differential Phase Centers of Rectangular Dielectric Rod Antennas - Richter, Jürgen; Garbas, Jens-Uwe; Schmidt, Lorenz-Peter (Proceedings of the European Microwave Conference, 2004)
Dielectric rod antennas of rectangular cross section are of increasing interest at millimeterwave frequencies. For many applications like e.g. densely packaged feed arrays for reflector/lens systems or electromagnetic field probes the exact knowledge of the phase center location is required. This paper will describe two efficient methods to determine the mean and differential phase center locations of such antennas by means of numerical electromagnetic field simulations and a subsequent analysis of the computed antenna phase pattern. Phase center locations of various dielectric rod antennas with rectangular cross section are presented and the influence of geometrical parameters and frequency on the phase center location are analyzed and discussed in detail. The theoretically derived results are also compared to measurements performed at X-band frequencies.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.LEH.meanan

Measurement of Phase Centers of Rectangular Dielectric Rod Antennas - Richter, Jürgen; Müller, matthias; Schmidt, Lorenz-Peter (IEEE International Antennas and Propagation Symposium, Monterey, California, 2004)
Dielectric rod antennas of rectangular cross section are of increasing interest at miliimeterwave frequencies. For many applications like e.g. densely packaged feed arrays for reflector/lens systems or electromagnetic field probes the exact knowledge of the phase center location is required. This paper will describe a simple experimental method to determine the phase center of antennas by means of a phase pattern measurement and a numerical least square fit procedure. For feed antennas the method can be adopted to the numerical aperture of reflector or lens systems. Phase center locations of various dielectric rod antennas with rectangular cross section are presented and the influence of geometrical parameters and frequency on the phase center are analysed and interpreted in detail.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.measur_5

Measurement Setup for Non-Destructive Complex Permittivity Determination of Solid Materials Using Two Coupled Coaxial Probes - Cenanovic, Amir; Schramm, Marcus; Schmidt, Lorenz-Peter (IMS 2011, 2011)
A non-destructive microwave measurement setup for broadband complex permittivity determination of solid materials over a frequency band from 0.05 GHz to 6 GHz is presented. The setup design was optimized for measurements of glass materials with planar and convex surfaces, but works with other dielectric materials as well. The measurement method is based on the near field coupling of two open-ended coaxial probes through the material under test (MUT). A theoretical modeling of this measurement configuration was performed, using a 3D full-wave electromagnetic field simulator. Two identical coaxial probes and an equivalent calibration kit, in order to perform a TRL calibration of the proposed setup, were designed. The calibration procedure of the measurement setup is explained and experimental results are presented.
lhft_intern.bib::Cenanovic11a

Micromachined Split-block Schottky-Diode Mixer for 600 GHz - Schür, Jan; Biber, Stephan; Gumbmann, Frank; Mottet, B.; Cojocari, O.; Schmidt, Lorenz-Peter; Hartnagel, H. (29th International Conference on Infrared and Millimeter Waves, 2004)
This paper presents simulation results for a 600 GHz micro-machined waveguide mixer with integrated horn antenna, a hybrid-integrated planar Schottky diode and IF filter structures on a quartz substrate. In addition to the simulated electrical performance we will show first approaches for the manufacturing of the split-block mixer by both micro-mechanical milling and silicon etching technology. ©2004 IEEE.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.microm

Millimeter wave frontend concepts and MMICs for automotive and communicationapplications - Schmidt, Lorenz-Peter; Adelseck, B; Guettich, U (MTT-Symposium, Workshop „Wireless Applications“, 1994)
lhft_intern.bib::Schmidt32

Millimeter-Wave Imaging With Optimized Sparse Periodic Array for Short-Range Applications - Gumbmann, Frank; Schmidt, Lorenz-Peter (IEEE Transactions on Geoscience and Remote Sensing, 2011)
lhft_intern.bib::Gumbmann2011

Millimeter-Wave Monolithic Integrated Circuits - Schmidt, Lorenz-Peter; Menzel, W; Adelseck, B; Guettich, U (International MMIC-Workshop ESA/ESTEC, 1986)
This paper summarizes the progress, trends, and technical issues associated with monolithic millimeter-wave integrated circuit technology. Presented first is background information which sets forth a description of the opportunities which spur this activity, and a summary of the important technical challenges. The technical challenges encompass aspects of: semicondutor material growth and processing; solid-state source performance; device and circuit characterization, de-embedding and modeling; and automated testing. Next, a discussion is provided of the semiconductor device types and circuit media which serve as building blocks for this technology. Device types treated here include sources, mixer/detectors, and modulators. The material offered relating to circuit media contrasts the attributes of monolithic approaches with those of waveguide and hybrid techniques. The paper concludes with a description of salient monolithic programs which benchmark the status of current effort in the U.S. This description includes a summary of important technical issues and research thrust
lhft_intern.bib::Schmidt21

Millimeter-wave monolithic integrated receiver circuits - Schmidt, Lorenz-Peter; Adelsecl, B; Colquhoun, A; Dämbkes, H (AGARD No. 482 Advances on Components for Active and Passive Airborne Sensors, 1990)
lhft_intern.bib::Schmidt18

MMICs for automotive and traffic applications - Coloquhoun, A; Schmidt, Lorenz-Peter (GaAs IC Symp, 1992)
A number of applications of microwave and, in particular, millimeter-wave MMICs (monolithic microwave integrated circuits) in automotive systems are under development. The authors review these applications and give the current status of some of these developments. The applications considered are sensors (both radar and radiometric), communication systems, and traffic control systems. MMICs for the following specific systems are considered: speed sensors, electronic toll collection, and collision avoidance rada
lhft_intern.bib::Schmidt24

MMIC technology in Europe for millimeter-wave applications (invitedpaper) - Dämbkes, H; Schmidt, Lorenz-Peter (GaAs92 - European GaAs Application Symposium, 1992)
lhft_intern.bib::Schmidt27

MOS-16: A New Method for In-Fixture Calibration and Fixture Characterization - Schramm, Marcus; Schür, Jan; Hrobak, Michael; Schmidt, Lorenz-Peter; Konrad, Michael (ARFTG, 2011)
lhft_intern.bib::Schramm11

Multi-Antenna Data Collector for Smart Metering Networks with Integrated Source Separation by Spatial Filtering - Quednau, Philipp; Trommer, Ralph; Schmidt, Lorenz-Peter (Frequenz, 2016)
Wireless transmission systems in smart metering networks share the advantage of lower installation costs due to the expandability of separate infrastructure but suffer from transmission problems. In this paper the issue of interference of wireless transmitted smart meter data with third party systems and data from other meters is investigated and an approach for solving the problem is presented. A multi-channel wireless m-bus receiver was developed to separate the desired data from unwanted interferers by spatial filtering. The according algorithms are presented and the influence of different antenna types on the spatial filtering is investigated. The performance of the spatial filtering is evaluated by extensive measurements in a realistic surrounding with several hundreds of active wireless m-bus transponders. These measurements correspond to the future environment for data-collectors as they took place in rural and urban areas with smart gas meters equipped with wireless m-bus transponders installed in almost all surrounding buildings.
lhft_intern.bib::Quednau2016

Multi-mode dual polarization 94 GHz monopulse antenna - Huder, B; Schmidt, Lorenz-Peter (AGARD No. 482 Advances on Components for Active and Passive Airborne Sensors, 1990)
lhft_intern.bib::Schmidt19

Multipath Sensor Based on GNSS for Passive Airborne Surveillance - Wachtl, Stefan; Koch, V.; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Passive radar systems are of great interest for several kinds of applications and therefore subject of actual research and development. One main application for passive radar systems is airborne surveillance, which includes the detection and tracking of airborne targets. Several passive radar systems based on terrestrial illumination have been demonstrated in the past. In passive radar applications based on satellite systems, a Global Navigation Satellite System (GNSS) can represent the radar transmitter, which illuminates the target, completed by a modified GNSS receiver, which analyses the radar signals. The advantages of this system would be the worldwide availability, the high number of transmitters and the coherent and well known signal structure. The main challenge in this system would be the extremely low signal power received on earth surface. In this paper, a multipath sensor for passive radar applications, which uses the Global Positioning System (GPS) L1 frequency as target illuminator, is demonstrated. Considerations about the expected signal power of multipath signals caused by a target are presented and confirmed through measurements. The main goal of this work is detecting, ranging and tracking a target in speed and distance over time. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.multip

Multiport Network Analysis at High Frequencies - Ziegler, Christof; Martius, Siegfried; Schmauß, Bernhard; Schmidt, Lorenz-Peter; Hocke, Ralf; Wohlgemuth, O. (6th IEEE Workshop , Signal Propagation on Interconnects, 2002)
This paper describes the problem of characterizing multiport networks at high frequencies, especially such devices which are stimulated by a common-mode or differential-mode source. An overview over the definition of mixed-mode S-parameters and their relation to nodal S-parameters is given. A measurement system is presented, which enables to measure all S-parameters of a 4-port with a 2-port network analyzer in an automated procedure. The functionality of this measurement system is described and possible ways for calibration are shown. ©2002 IEEE.
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.multip

Multistatic GNSS Receiver Array for Passive Air Surveillance - Wachtl, Stefan; Koch, Volker; Westphal, Robert; Schmidt, Lorenz-Peter (Frequenz, 2016)
The performance of a passive air surveillance sensor based on Global Navigation Satellite Systems (GNSS) is mainly limited by the receiver noise efficiency, the achievable signal processing gain and the radar cross section (RCS) of an airplane. For surveillance applications large detection ranges as well as a high probability of detection are crucial parameters. Due to the very low GNSS signal powers received on the earth’s surface, high radar cross sections are mandatory to achieve detection ranges for airplanes at some kilometers distance. This paper will discuss a multistatic transmitter and receiver arrangement, which is indispensable to get a reasonable detection rate with respect to a hemispheric field of view. The strong performance dependency of such a sensor on the number of transmitters and receivers will be shown by means of some exemplary simulation result
lhft_intern.bib::Wachtl2016

Multistatic/MIMO Close-Range Imaging Radar: Realization and Challenges - Ahmed, S.; Adametz, Julian; Gumbmann, Frank; Schiessl, Andreas; Schmidt, Lorenz-Peter; Vossiek, Martin (IEEE IMS 2014 Workshop on MIMO Radar Techniques and Frontends for Localization and Imaging, 2014)
lhft_intern.bib::Ahmed2014

Multistatic/MIMO Close-Range Imaging Radar: Theory and Concepts - Adametz, Julian; Ahmed, S.; Gumbmann, Frank; Schiessl, Andreas; Schmidt, Lorenz-Peter; Vossiek, Martin (IEEE IMS 2014 Workshop on MIMO Radar Techniques and Frontends for Localization and Imaging, 2014)
lhft_intern.bib::Adametz2014

Multistatic mm-Wave Imaging with Planar 2D-Arrays - Ahmed, S. S.; Schießl, Andreas; Schmidt, Lorenz-Peter (GeMiC 2009, 16 - 18 March, München, Germany, 2009)
This work reports measurement results for the scanning of 2D and 3D objects in W-band (75 to 110 GHz) using active 2D planar arrays in multistatic configuration with digital beamforming technique. The image quality of the object reflectivity depends mainly on the frequency band, array configuration, signal polarization, and focusing method. Multistatic measurements allow for higher dynamic range, reduced antennas count and the feasibility for cross-polarization measurements. Measurements meet the theoretical expectation and the simulation results down to 4 mm resolution. Two multistatic arrays will be presented and compared in terms of image resolution, antennas count, SNR and digital processing needed.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.multis
Keywords: Back-propagation; Digital beamforming; Imaging; Mm-wave; Point spread function; Signal to noise ratio

Multistatic Short Range Ka-Band Imaging System - Gumbmann, Frank; Tran, Hue Phat; Weinzierl, Jochen; Schmidt, Lorenz-Peter (GeMIC 2009, München, March, 2009)
This paper presents the concept of a Ka-Band (26.5 - 40 GHz) multistatic active short range imaging system. The motivation for this work was the development of a fast scanning imaging system for non destructive testing (NDT) or securityscenarios. The goal was to derive a 3D reconstruction of thedevice under test (DUT). The imaging system consists of a linear receive array and spatially distributed transmitters with non focussing antenna elements. This transmit/receive array receiveris moved perpendicular to the array dimension. By switching device between each transmitter and simultaneous reception of the IDUT)scattered field by each receiver, a fast sampling of the 2D aperture plane is achieved. Due to unfocussed antenna elements Ynumerical reconstruction algorithms have to be applied for a lateral resolution. An aperture synthesis concept is presented R to reconstruct the raw data. It is based on the separation 7R-7of the reconstruction kernel into a horizontal and a vertical part. Range resolution is achieved by a broadband stepped frequency continuous wave.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.multis_1

Near Field mm-Wave Imaging with Multistatic Sparse 2 D-Arrays - Ahmed, S. S.; Schießl, Andreas; Schmidt, Lorenz-Peter (Proceedings of the 6th European Radar Conference, 2009)
A near field application of multistatic 2D sparse arrays designed based on an effective aperture concept is presented. Several test arrays which utilize this concept are introduced along with simulation and measurement results for near field operation at 100 GHz. High reduction in the needed number of transmit and receive modules is verified along with the drawbacks in the image quality. Good agreement between measurements and simulations is demonstrated.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.nearfi

Non Destructive Complex Permittivity Determination of Glass Material with Planar and Convex Survace - Cenanovic, Amir; Martius, Siegfried; Kilian, A.; Schür, Jan; Schmidt, Lorenz-Peter (6th German Microwave Conference, 2011)
lhft_intern.bib::Cenanovic11

Non-destructive testing of glass fibre reinforced plastics with a full polarimetric imaging system - Nezadal, Martin; Schür, Jan; Schmidt, Lorenz-Peter (Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2014 39th International Conference on, 2014)
A full polarimetric imaging system for the nondestructive testing of glass fibre reinforced plastics in the W-Band (75 GHz to 110 GHz) is presented. It is capable of detecting defects in depths of up to 14.5mm, and 0.5mm near the backside of the samples. The full polarimtric information eases the defect detection, since it is not sensitive for the reflection from the backside.
lhft_intern.bib::NezadalIRMMW14

Non-destructive testing of glass fibre reinforced plastics with a synthetic aperture radar in the lower THz region - Nezadal, Martin; Schür, Jan; Schmidt, Lorenz-Peter (Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2012 37th International Conference on, 2012)
The non-destructive testing (NDT) of glass fibre reinforced plastics (GFRP) becomes more and more important. A test setup using a synthetic aperture radar (SAR) at frequencies of 220 - 325 GHz was set up to detect artificial defects in the probe. The paper will present experimental results and will furthermore address the challenges of imaging GFRP samples in a reflection geometry setup. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.nondes

Novel Coupled Microstrip Wideband Filters with Spurious Response Suppression - Rehner, Robert; Schneiderbanger, Dirk; Sterns, Michael; Martius, Siegfried; Schmidt, Lorenz-Peter (European Microwave Conference 9-12. Oct., 2007)
Wideband coupled line filters with spurious response suppression (2f 0) in the millimeter wave range are reported. The first filter exhibits a relative bandwidth of 62% with a return loss better than 20 dB and a suppression of the second spurious passband of more than 40 dB. The very high necessary couplings to achieve that large bandwidth in combination with the spurious suppression are realized by removing partially the ground metallization beneath the proposed coupling sections. The filters are directly compatible to microstrip circuits without the need for complicated transitions. They do not require techniques like substrate suspension or dielectric overlay to match the evenand odd-mode phase velocities, but are realizable on a classical substrate with ground. Further, simulation and measurement results of a second, high selective filter (11th order) with an even higher bandwidth of 78% are shown. Measurement and simulation results are fitting very well. © 2007 EuMA.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.novelc

Novel Fully Electronic Active Real-Time Millimeter-Wave Imaging System based on a Planar Multistatic Sparse Array - Ahmed, Sherif Sayed; Schießl, Andreas; Schmidt, Lorenz-Peter (International Microwave Symposium 2011, 2011)
The interest on active millimeter-wave and microwave imaging systems is increasing nowadays due to their utilization in security, medical, and industrial applications. Imaging systems using monostatic arrays suffer from the high number of antenna positions, making a fully electronic solution very costly and impractical. Multistatic arrays, however, offer the chance for high reduction factors in the number of antennas, and then allow for fully electronic solutions. Here, a new array architecture is presented, which is suitable for real-time operation and is capable of delivering high image quality in means of resolution and dynamic range. An example array is demonstrated for operation from 72 to 80 GHz. The imaging system hardware is introduced, along with imaging results of human
lhft_intern.bib::Ahmed11

Novel Tunable Hexaferrite Bandpass Filter Based on Open-Ended Finlines - Sterns, Michael; Rehner, Robert; Schneiderbanger, Dirk; Martius, Siegfried; Schmidt, Lorenz-Peter (IMS 2009, Boston, June, 2009)
In this paper a novel tunable bandpass filter based on open ended finlines is presented. Hexagonal ferrite spheres are used as resonators to cover a tuning frequency range from 39GHz to 68GHz. The measured insertion loss of the filter varies from 5.3dB to 7dB with a typical 3dB-Bandwidth between 300MHz and 400MHz. An off-resonance isolation of about 60dB is achieved although only two spheres are used. By employing finlines for the external coupling of the resonator spheres, broadband transitions to microstrip line can be designed easily, thus simplifying the integration into a planar transmission line environment. Furthermore, the use of finlines allows to cover a considerably larger operating range than the classical rectangular waveguide based coupling structures do. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.novelt

Novel Tunable Hexaferrite Bandpass Filter Based on Rectangular Waveguide Coupled Shielded Coplanar Transmission Lines - Sterns, Michael; Schneiderbanger, Dirk; Rehner, Robert; Martius, Siegfried; Schmidt, Lorenz-Peter (IEEE MTT-S International Microwave Symposium June, 2008)
In this paper a novel tunable high isolation bandpass filter is presented. The filter consists of two shielded coplanar transmission lines coupled by a rectangular waveguide. Hexagonal ferrite spheres are used to cover a tuning frequency range from 50 to 80GHz. Measurement results up to 69GHz are shown. The measured insertion loss of the filter lies between 7.1 and 9.3dB. An off-resonance isolation better than 60dB is achieved what is extraordinarily high for a two spheres filter. The typical 3dB-bandwidth is about 250MHz. As planar transmission lines are used, the filter can be integrated into a coplanar or microstrip environment easily what is advantageous for the construction of highly integrated modules. The operating frequency range can be expanded up to 80GHz by replacing the 1.85mm-connectors by lmm-connectors or using other suitable waveguide transitions, thus covering considerably more bandwidth than rectangular waveguide based coupling structures. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.novelt

Numerical Calculation of Stimulated Brillouin Scattering and its Suppression in Raman Fiber Amplifiers - Engelbrecht, Rainer; Bayer, M.; Schmidt, Lorenz-Peter (16th Int. Conference on Lasers and Electrooptics, CLEO Europe, München, 23.- 27.Juni, 2003)
In this paper, simulated Brillouin scattering in Raman fiber amplifier was numerically calculated. The theoretical results show that much more power could be transferred from the pump to the signal in Raman fiber amplifier with no SBS and Brillouin frequency shift in a given fiber depends on temperature and on mechanical strain. And spatially variable longitudinal strain distribution in standard fibers for SBS suppression in active devices was proposed. © 2003 IEEE.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.numeri

Optimally shaped reflectors for Gaussian beam transformation - Schildbach, Christian; Schmidt, Lorenz-Peter (IEEE Conference on Antenna Measurements & Applications (CAMA), 2014)
For focusing reflectors usually paraboloidal and ellipsoidal shapes are used, which are a first degree approximation to an optimal beam transformer. In this paper, the design of such an optimally shaped reflector is described, using basic numerical procedures and common CAD software. The complexity of the described procedure is not much higher than the design of paraboloidal or ellipsoidal reflectors. Measurement data is presented to confirm the functionality of the designed reflector at frequencies beyoned 200 GHz.
lhft_intern.bib::Schildbach2014

Optimization of a fast scanning millimetre-wave short range SAR imaging system - Gumbmann, F; Tran, H; Weinzierl, Jochen; Schmidt, Lorenz-Peter (European Microwave Conference October, 2007)
This paper presents the development of a W-band short range imaging system for security and non-destructive testing applications, which uses an unfocused measurement setup employing SAR algorithms in order to focus the image numerically. The active imaging system offers the possibility to get a broadband frequency response from each pixel in the measurement plane. For real-time applications a fast scanning, monostatic virtual antenna concept has been developed and optimized. The monostatic setup is demonstrated in two different configurations, on the one hand using a quasioptical, broadband diplexer with high decoupling between transmitter and receiver channel and on the other hand a very compact setup using a commercially available high directivity waveguide coupler. The measurement setups are compared with special respect to their RF-performance. Experimental results on specific test objects are presented to prove the performance of the fast short range SAR imaging syste
lhft_intern.bib::Gumbmann07a

Optimized method for achieving accurate signals for “True-Mode” S-parameter measurements - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter; Konrad, Michael (45^th European Microwave Conference, 2015)
Due to the capabilities of modern vector network analyzers (VNAs), the usage of “True-Mode”-signals for characterizing and testing active differential devices is quite convenient. Nevertheless in cases, in which the device under test (DUT) and/or the measurement setup introduces a coupling between the required stimulus signals, current methods require some iteration time to achieve the desired phase and amplitude settings. In this paper a new approach will be introduced, which leads to an optimized testing time which can be crucial especially in industrial production tes
lhft_intern.bib::Schramm2015

Outer Body Skin with an Integrated Antenna - Fuchs, Manuel; Kilian, Andreas; Brocka, Zaneta; Schmachtenberg, Ernst; Schmidt, Lorenz-Peter (Kunststoffe International, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.LEH.outerb

Oxidized Hyaluronic Acid-Gelatin-Based Hydrogels for Tissue Engineering and Soft Tissue Mimicking - Kuth, Sonja; Karakaya, Emine; Reiter, Nina; Schmidt, Lorenz-Peter; Paulsen, Friedrich; Tessmar, Jorg; Budday, Silvia; Boccaccini, Aldo R. (Tissue Engineering - Part C: Methods, 2022)
Hydrogels are ideal materials for mimicking and engineering soft tissue. Hyaluronic acid is a linear polysaccharide native to the human extracellular matrix. In this study, we first develop and characterize two hydrogel compositions built from oxidized HA and gelatin with and without alginate-di-aldehyde (ADA) crosslinked by ionic and enzymatic agents with potential applications in soft tissue engineering and tissue mimicking structures. The stability under incubation conditions was improved by adjusting crosslinking times. Through large-strain mechanical measurements, the hydrogels' properties were compared to human brain tissue and the samples containing ADA revealed similar mechanical properties to the native tissue specimens in cyclic compression-tension. In vitro characterization demonstrated a high viability of encapsulated mouse embryonic fibroblasts and a spreading of the cells in case of ADA-free samples.
CRIS-Team WoS Importer:2022-05-20

Parasitic Effects in Broadband Chip Modules Based on Multilayer LTCC Technology - Nisznansky, Martin; Ziegler, Christof; Schür, Jan; Schmidt, Lorenz-Peter; Hocke, Ralf; Wohlgemuth, Oliver (Proceedings of the 33rd European Microwave Conference, 2003)
In this paper we refer to typical parasitic and spurious effects that must be considered for the design of broadband modules. We focus on the discussion of problems like resonances and parasitic propagation modes which are typical for interconnects realized in a multilayer LTCC environment. For understanding such effects, full wave electromagnetic analysis of frequently used interconnects was performed. Then appropriate design measures were taken to avoid these undesirable effects. Further optimization steps on interconnects are described which minimize distortion of high speed digital signals. Resulting optimized interconnect structures can then be used as standard solution with guaranteed electrical performance for particular LTCC processes. Major part of the presented results were verified by measurements.

Parasitic Effects in Broadband Chip Modules Based on Multilayer LTCC Technology - Nisznansky, Martin; Ziegler, Christof; Schür, Jan; Schmidt, Lorenz-Peter; Hocke, Ralf; Wohlgemuth, O. (33rd European Microwave Conference, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.parasi

Permittivity Measurement Techniques at 24 GHz for Automative Polymer Composites Including Thin Films and Paint Foils - Kilian, Andreas; Weinzierl, Jochen; Schmidt, Lorenz-Peter (Proceedings of the German Microwave Conference, 2008)
Two different measurement techniques for the determination of complex permittivities of automotive polymer composites used as bumper or car body panels at 24 GHz are presented. The materials in focus of this research are basically plastics for injection molding like polycarbonate and its derivatives. The composites include thin dielectric films and paint foils for coloring and lamination of injection molded panels. The advantages and inconveniences of multi-layer measurements in rectangular waveguides and an open resonator are demonstrated. Additionally, an approach is proposed for further investigations on permittivity and loss tangent of automotive dielectrics in the millimeter-wave region.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.permit

Phase Error Sensitivity in Multistatic Microwave Imaging Systems - Schießl, Andreas; Ahmed, S. S.; Genghammer, A.; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Current digital-beamforming multistatic mm-wave array designs show superior near field imaging performance. Therefore, mm-wave imaging systems based on these concepts are suitable for a variety of security, medical and industrial applications. The theoretically achieved array performance can be degraded by noise and unwanted signals within the actually implemented systems. In this work, the sensitivity of such systems on certain types of systematic errors within its signal processing chain including the system error correction mechanism is discussed and analyzed. Effects of errors within the reconstructed images are demonstrated, and methods to reduce the effects of some dominant error signals are proposed. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.phasee
Keywords: error correction; microwave imaging; multistatic radar; signal processing

Planar D-Band Frequency Doubler and Y-Band Tripler on PTFE Laminates - Hrobak, Michael; Sterns, M.; Schramm, Marcus; Stein, Wadim; Poprawa, F.; Ziroff, A.; Schür, Jan; Schmidt, Lorenz-Peter (Proceedings of the 38th International Conference on Infrared, Millimeter and Terahertz Waves IRMMW-THz 2013, 2013)
To extend the frequency range of existing short-range radar modules for industrial applications, millimeter-wave frequency multipliers based on cost-effective PCB technology are required. This paper describes a zero-bias D-band frequency doubler and Y-band frequency tripler based on pure PTFE material and the commercially available DBES105a diode from United Monolithic Semiconductors (UMS). At an input drive level range of 16 dBm to 18 dBm the multipliers deliver output power levels POUT ∈ [5, -5] dBm from 100 GHz to 160 GHz and POUT ∈ [-11, -20] dBm from 180 GHz to 230 GHz. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.planar

Planar integrated components perform up to 110 GHz - Menzel, W; Meinel, H; Rembold, B; Schmidt, Lorenz-Peter (Microwaves, 1982)
lhft_intern.bib::Schmidt10

Planar integrated harmonic mixers for use up to 150 GHz - Schmidt, Lorenz-Peter; Menzel, W (MIOP `87, 1987)
lhft_intern.bib::Schmidt15

Planar Varistor Mode Schottky Diode Frequency Tripler Covering 60 GHz to 110 GHz - Hrobak, Michael; Sterns, Michael; Schramm, Marcus; Stein, Wadim; Schmidt, Lorenz-Peter (Proceedings of the International Microwave Symposium 2013, 2013)
Frequency extender modules of vector network analyzers (VNA) and signal generators, as well as front end modules of semiconductor automatic testsystems (ATS) make use of broadband resistive diode frequency multipliers. We present the design and construction of a planar varistor tripler utilizing commercial gallium arsenide (GaAs) Schottky diodes on thin-film processed alumina (Al 2O3) substrate. Synthesis is based on a co-simulation procedure between 3D electromagnetic field (EM) and nonlinear circuit simulations. Measurement data over the focused output frequency range from 60 GHz to 110 GHz is presented. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.planar_1
Keywords: 1 mm coaxial connector; Planar W-band multiplier; Schottky diode frequency multiplier; Varistor tripler

Planar Zero Bias Schottky Diode Detector Operating in the E- and W-Band - Hrobak, Michael; Sterns, Michael; Schramm, Marcus; Stein, Wadim; Schmidt, Lorenz-Peter (Proceedings of the 43th European Microwave Week, 2013)
Schottky diode detectors are the method of choice for many scalar power measurement applications in the millimeter wave frequency range. Power monitoring of forward and backward travelling waves is especially important within signal generator frequency extension modules and front end modules of semiconductor automatic test systems (ATS). We present the synthesis and characterisation of a planar zero bias Schottky diode (ZBD) detector that covers an input frequency range of 60 GHz to 110 GHz. The planar design is based on thin-film processed Al2O3 substrate. The utilized gallium arsenide (GaAs) diodes are commercially available from Virginia Diodes, Inc. (VDI). The presented measurement data is compared to results from 3D electromagnetic field (EM) and nonlinear circuit simulations. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.planar_5
Keywords: W-Band DC Block; W-Band Detector; W-Band RF Choke; Zero Bias Schottky Diode

Possible large market applications of microwaves: Market aspectsand technological approaches (invited talk) - Schmidt, Lorenz-Peter (European Microwave Conference, 1994)
lhft_intern.bib::Schmidt30

Quasiplanar 3 dB hybrid for millimetre-wave integrated circuits - Callsen, H; Schmidt, Lorenz-Peter (Electronics Letters, 1982)
lhft_intern.bib::Schmidt12

Radio Frequency Modeling of Receive Coil Arrays for Magnetic Resonance Imaging - Stumpf, Christopher; Malzacher, Matthias; Schmidt, Lorenz-Peter (2018)
The numerical calculation of the signal-to-noise ratio (SNR) of magnetic resonance imaging (MRI) coil arrays is a powerful tool in the development of new coil arrays. The proposed method describes a complete model that allows the calculation of the absolute SNR values of arbitrary coil arrays, including receiver chain components. A new method for the SNR calculation of radio frequency receive coil arrays for MRI is presented, making use of their magnetic B1−" role="presentation">B−1 transmit pattern and the S-parameters of the network. The S-parameters and B1−" role="presentation">B−1 fields are extracted from an electromagnetic field solver and are post-processed using our developed model to provide absolute SNR values. The model includes a theory for describing the noise of all components in the receiver chain and the noise figure of a pre-amplifier by a simple passive two-port network. To validate the model, two- and four-element receive coil arrays are investigated. The SNR of the examined arrays is calculated and compared to measurement results using imaging of a saline water phantom in a 3 T" role="presentation">3 T scanner. The predicted values of the model are in good agreement with the measured values. The proposed method can be used to predict the absolute SNR for any receive coil array by calculating the transmit B1−" role="presentation">B−1 pattern and the S-parameters of the network. Knowledge of the components of the receiver chain including pre-amplifiers leads to satisfactory results compared to measured values, which proves the method to be a useful tool in the development process of MRI receive coil arrays.
Keywords: receive coil array; SNR modeling; MRI; pre-amplifier noise; noise coupling

Radiometer Design for Short Range Imaging at 2.5 THz - Huber, K.; Biber, Stephan; Rehm, Guenther; Schulz, R.; Brand, Hans; Schmidt, Lorenz-Peter (Proceedings of the Open Symposium on Propagation and Remote Sensing, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.radiom

Recent developments and concepts leading to advanced microwave andmm-wave phased array antennas - Huder, B; Schmidt, Lorenz-Peter; Adelseck, B; Feldle, H; Dämpkes, H (International MMIC-Workshop ESA/ESTEC, 1991)
lhft_intern.bib::Schmidt22

Reflection Ellipsometry with a Polarimetric Multistatic Array for Short Range Imaging Applications - Cenanovic, Amir; Gumbmann, Frank; Schmidt, Lorenz-Peter (Asia-Pacific Microwave Conference, 2011)
This paper presents an approach for the detection of dielectric layers on human bodies and the determination of their dielectric constant with single frequency measurement data in the W-band (75-110 GHz). The measurements were performed with a polarimetric multistatic array, which was optimized for short range applications. The scattering matrix of each resolution element was analyzed via the reflection ellipsometry method, adopted from optics. For millimeter wave imaging techniques, used in the field of nondestructive testing (NDT) and for security applications, this measurement approach offers an promising alternative to the time domain analysis, which requires broadband data.
lhft_intern.bib::Cenanovic2011b

Rigorous Computation of the Frequency Dependant Properties of Filters and Coupled Resonators Composed from Transverse Microstrip Discontinuities - Schmidt, Lorenz-Peter (European Microwave Conference, 1980)
A numerically efficient method is presented, which yields the propagation constants and the field distributions of basic and higher order modes of shielded microstrip lines. Upon this basic a mode matching technique is applied in order to calculate the frequency dependant generalized scattering matrices of transverse microstrip discontinuities like impedance steps and open ends. From these discontinuities several microstrip components like filters, transverse gaps, and coupled resonators can be composed. Important effects like convergence behaviour, numerical stability, and the influence of higher order propagating and not propagating modes have been studied, and some interesting numerical and experimental results are presente
lhft_intern.bib::Schmidt80c

Robust DOA Estimation of SSR Signals for Aircraft Positioning - Reck, Christoph; Berold, U.; Schmidt, Lorenz-Peter (RWW, 2011)
lhft_intern.bib::Reck2011

Rx-Tx Analog Front-End Module with 2 x 96 Channels for mm-Wave ImagingSystems - Schiessl, A.; Juenemann, R.; Schmidt, Lorenz-Peter (42nd European Microwave Week, 2012)
Active millimeter-wave imaging systems are increasingly utilized in security, medical and industrial applications. At E-Band frequencies, such systems integrate more than three thousand antennas on 2 m × 1 m aperture. Commercial success of those systems requires cost efficient but precise manufacturing technologies to build highly integrated modular mm-wave front ends. Here, a module for a new sparse imaging array architecture is presented. The module is manufactured using a unique mm-wave chip-on-board technology. It operates from 70 GHz to 80 GHz, and integrates 48 MMICs and several thin film ceramic components.
lhft_intern.bib::Schiessl2012euwm

Schottky-Structures for THz-Applications based on Quasi-Vertical Design-Concept - Cojocari, O.; Sydlo, C.; Hartnagel, H.; Biber, Stephan; Schür, Jan; Schmidt, Lorenz-Peter (16th International Symposium on space Terahertz Technology ISSTT 2005, Göteborg, Sweden, May, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.schott

Sensitive Simultaneous Detection of CO and CO_2 with Commercial DFB Diode Lasers - Engelbrecht, Rainer; Brand, Hans; Schmidt, Lorenz-Peter (Proceedings, IRS2 (6. Conf. On Infrared Sensors and Systems, Erfurt 2000), 2000)
UnivIS-Import:2015-04-16:Pub.2000.tech.IE.LEH.sensit

Sensitive Simultaneous Detection of CO and CO_2 with Commercial DFB Diode Lasers for Optical Communication Systems - Engelbrecht, Rainer; Brand, Hans; Schmidt, Lorenz-Peter (2000)
lhft_intern.bib::thirty_years_LHFT_437

Short Range Imaging with Optimized Sparse Array - Gumbmann, Frank; Schmidt, Lorenz-Peter (EuSAR, Aachen, 7.06.-10.6., 2010)
This paper presents a MIMO imaging system on the basis of a hybrid concept with synthetic aperture radar (SAR) and digital beam forming (DBF). By moving a multistatic linear array perpendicular to the array dimension a two dimensional aperture is sampled. The scope of application is the field of non destructive testing (NDT) and security systems. Thus the frequency range 75-90 GHz seems to be a good compromise between lateral resolution and penetration depth. A moderate number of transmit and receive channels is achieved by a sparse periodic array (SPA) design. Since this is a far field approach, ambiguities are not well suppressed in the near field point spread function of the sparse array. Therefore an optimized array was developed as well as a post processing algorithm on the basis of a notch filter. This notch filter is applied to attenuate the main part of the ambiguous energy in the doppler spectrum. Results are demonstrated with simulated and measured data.
lhft_intern.bib::Gumbmann10b

Silicon-Micromachining and Electrical Characterization of a 600 GHz Schottky-Diode Mixer with Integrated Octagonal Horn Antenna - Biber, Stephan; Schür, Jan; Cojocari, O.; Hartnagel, H.; Schmidt, Lorenz-Peter (4th ESA Workshop on Millimetre Wave Technology and Applications, Helsinki, Finnland, February, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.silico

Simulation and Measurement of Interconnect Structures for High Speed Digital Systems - Nisznansky, Martin; Ziegler, Christof; Martius, Siegfried; Schmidt, Lorenz-Peter; Müller, J. (Signal Propagation on Interconnects, 2002)
Results of electromagnetic simulations and measurements of simple interconnect structure are discussed in this paper. The presented structure was realised on LTCC multilayer board which are suitable for manufacturing of multichip modules for next generation communication systems with clock rates in the 10-100GHz range. From the presented results it is possible to obtain an impression about distortion of high speed digital signals after passing this or similar interconnect structures. Precision microwave measurement techniques that are important for verification of such simulations are discussed, too. © 2002 IEEE.
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.simula

Size-Reduction and Suppression of Cavity-Resonances in Hybrid mm-Wave Antennas for Polarimetric Measurements - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Size and feed structure are some of the important constraints for using antenna-elements in multi-element two-dimensional arrays, where easy planar integration with transceiver chips is essential. This applies especially when differential signaling and adaptable polarization is required. Based on a balanced-fed patch-excited cavity-backed horn antenna (hybrid antenna), feeding concepts and approaches to reduce size are discussed and evaluated in this paper. The influence of the substrate integrated cavity is analyzed and methods to overcome the restrictions are presented, together with simulated and measured results. The optimized antennas achieve a relative bandwidth of more than 17% for 10 dB return loss, a gain of more than 5 dBi as well as symmetric and homogeneous radiation patterns in amplitude and phase with low cross-polarization. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.sizere
Keywords: Antenna arrays; Antenna feeds; Aperture coupled antennas; Cavity resonators; Horn antennas; Millimeter wave radar; Radar imaging; Radar polarimetry

Size-reduction and suppression of cavity-resonances in hybrid mm-wave antennas for polarimetric measurements - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (43rd European Microwave Conference, 2014)
Size and feed structure are some of the important constraints for using antenna-elements in multi-element two-dimensional arrays, where easy planar integration and appropriate matching with transceiver chips are essential. This applies especially when differential signaling and adaptable polarization are required. Based on a balanced-fed patch-excited cavity-backed horn antenna (hybrid antenna), feeding concepts, and approaches to reduce size are discussed and evaluated in this paper. The influence of the substrate-integrated cavity is analyzed and methods to overcome the restrictions are presented, together with simulated and measured results. The antenna elements are evaluated with regard to their use in multistatic and polarimetric sparse arrays, which will be briefly introduced. The optimized antennas achieve 10 dB return loss, a gain of more than 5 dBi as well as symmetric and homogeneous radiation patterns in amplitude and phase with low cross-polarization in the desired frequency-band of operation between 70 and 80 GH
lhft_intern.bib::Methfessel2013n

Space-Resolved Measurement and 2D-Mapping of Material Parameters Using Multi-Angle Reflection Ellipsometry in W-Band - Cenanovic, Amir; Schmidt, Lorenz-Peter (Proceedings of the International Microwave Symposium 2013, 2013)
In this paper a free-space method is presented for space-resolved measurement of the relative permittivity and thickness of a single layer dielectric material in the W-band. The reflection of parallel and perpendicularly polarized waves from the material under test is measured with a polarimetric linear array. Synthetic aperture focusing of the raw data is performed, in order to obtain space-resolved reflection coefficients, from which the material parameters are determined using the spectroscopic multi-angle reflection ellipsometry technique. Results of the proposed method are presented in the frequency range of 75-95 GHz for low loss materials with a few millimeters of thickness. The relative uncertainty in determining the thickness and ε′ of Teflon is 2% and 3% respectively. The capability of the method to accomplish space resolved material characterization is demonstrated by two dimensional mapping of the relative permittivity of Teflon with a high accuracy. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.spacer
Keywords: Ellipsometry; Permittivity; Radar imaging

Sparse Linear Array Design for a Short Range Imaging Radar - Gumbmann, Frank; Tran, Hue Phat; Schmidt, Lorenz-Peter (EuMW, 28.09-2.10., Rom, 2009)
This paper presents the design of an active short range imaging system in the Ka-band (26.6 - 40 GHz). The sensor is a multistatic linear array which is moved perpendicular to the array dimension for the purpose of 3D imaging. By sequentially switching on the transmitters and simultaneous reception of the scattered field by each receiver, a fast sampling of the 2D aperture plane is achieved. To reduce the number of parallel receive channels, a thinned array on the base of sparse periodic arrays (SPA) was developed. Due to non focussing antenna elements, numerical reconstruction algorithms, for near field conditions, have to be applied for a high lateral resolution. First simulation results verify the imaging quality of this concept and the functionality of the proposed reconstruction algorithm. © 2009 EuMA.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.sparse

Sparse MIMO Array for Multi-Angle Reflection Ellipsometry - Cenanovic, Amir; Schmidt, Lorenz-Peter (IEEE International Conference on Wireless Information Technology and Systems 2012, 2012)
The combination of the reflection ellipsometry method with a polarimetric imaging system illustrated in Fig. 1(a) offers a promising approach for robust material characterization of dielectric samples from the phase difference of the (p) and (s) -polarized complex images Rp and Rs [1, 2]. Since the phase difference arg(Rp/Rs) depends on the incidence angle α (Fig. 1(b)), a higher sensitivity and robustness in parameter estimation is achieved from measurements at different angles. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.sparse

Spatial Filtering and Equalization for SSR Signal Detection in a Multipath Environment - Reck, Christoph; Reuther, M.; Berold, Ulrich; Schmidt, Lorenz-Peter (6th German Microwave Conference, 2011)
Detection of Secondary Surveillance Radar (SSR) signals is highly error prone in scenarios where multipath propagation and transponder interference is involved. The proposed method largely improves this situation by iteratively combining smart antenna and classical equalization approaches. A large dataset of SSR replies, recorded at problematic sites of Frankfurt Airport by a multichannel receiver is used for verification.
lhft_intern.bib::Reck11a

Spatial Resulution of Millimeter Wave Imaging at 75 - 100 GHz and 600 GHz - Tran, Hue Phat; Gumbmann, Frank; Weinzierl, Jochen; Schmidt, Lorenz-Peter (German Microwave Conference, Karlsruhe, March, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.spatia

Spectral Domain Analysis of Dominant and Higher Order Modes in Fin-Lines - Schmidt, Lorenz-Peter; Itoh, T (IEEE Transactions on Microwave Theory and Techniques, 1980)
The spectral domain analysis is applied to deriving dispersion characteristics of the dominant, higher order modes in the fin-line structures. Numerical results are compared with those by a modified spectral domain technique as well as other dat
lhft_intern.bib::Schmidt80b

STIREEM - A new High Resolution Microwave Imaging Principle - Brand, Hans; Martius, Siegfried; Schmidt, Lorenz-Peter; Schür, Jan; Weinzierl, Jochen; et al. (Proceedings of the German Microwave Conference, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.stiree_8

STIREEM - A Novel Technique for High Resolution Microwave Imaging - Brand, Hans; Dexl, A.; Hagen, Johannes; Kellnberger, S.; Martius, Siegfried; Schmidt, Lorenz-Peter; Schür, Jan; Weinzierl, Jochen (Proceedings of the European Microwave Association, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.stiree

Substrattechnologien für planar integrierte Mikro- und Millimeterwellenschaltungen - Schmidt, Lorenz-Peter; Methfessel, Sebastian Dirk; Schneiderbanger, Dirk; Rehner, Robert; Sterns, Michael; Kilian, Andreas; Nisznansky, Martin (Kooperationsforum Leiterplattentechnologie, Nürnberg, 22.01.2008, S. 95-124, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.substr

Systematic Quality Assessment of Schottky Diodes for THz-Applications - Biber, Stephan; Cojocari, O.; Mottet, B.; Rehm, Guenther; Schmidt, Lorenz-Peter (3rd ESA Workshop on Millimetre Wave Technology and Applications, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.system

Taschenbuchs der HF-Technik (Meinke-Gundlach) - Schmidt, Lorenz-Peter; Adelseck, B (Taschenbuchs der HF-Technik (Meinke-Gundlach), 1986)
lhft_intern.bib::Schmidt14

Technological Issues for Micromachining of New Passive THz-Components Based on Deep-Trench Silicon Etching - Biber, Stephan; Schür, Jan; Schmidt, Lorenz-Peter (29th International Conference on Infrared and Millimeter Waves, 2004)
We present a survey of the application of micromachining techniques for the fabrication of THz-components. Micro-machining of new THz- devices based on deep trench etching of silicon will be discussed with respect to its capability to generate complex 3-dimensional geometries with high aspect ratios (ARs) and to meet the high mechanical requirements for THz-components. First results for the application of deep trench etching for the design of a branch-line coupler for 600GHz will be discussed. We will emphasize the potential of silicon based microstructures for the manufacturing of new devices and focus on technological issues. © 2004 IEEE.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.techno

Temperature Sensitivity of Large Digital-Beamforming Multistatic mm-Wave Imaging Systems - Schießl, Andreas; Ahmed, Sherif Sayed; Genghammer, Andreas; Schmidt, Lorenz-Peter (IEEE International Microwave Symposium 2013, 2013)
Large multistatic mm-wave imaging systems have recently been developed and proved to be efficient for security applications. This work analyzes the effects caused by temperature changes on the imaging performance of a state-of-the-art system. The temperature dependent phase drift of a single measurement channel is characterized. A linearized model for the phase drifts in the RF channels is thus derived This model is applied to simulate for systematic phase drifts in the recorded raw data of the imaging system at different temperature profiles. Afterwards, images are reconstructed using modified raw data. Accordingly, the degradation in the imaging performance due to temperature changes is presented in terms of image quality and the associated point spread functions. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.temper
Keywords: Chip-on-board; Microwave imaging; Millimeter wave technology; Multichip modules; Temperature dependence

Threat Object Classification with a Close Range Polarimetric Imaging System by Means of H-alpha Decomposition - Adametz, Julian; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
In this paper, an approach to differentiate between various dielectric threat objects in security applications is investigated. The scattering information in form of the Sinclair matrix of relevant scenarios is gained from a fully polarimetric, monostatic synthetic aperture radar (SAR). A possible polarimetric calibration procedure is presented. The radar data are processed with the H-α decomposition algorithm. The H-α scattering characteristics of threat objects are analyzed in terms of a weighted averaging. It is shown that an object classification is possible even for threat objects conceiled under thick layers of clothing. Measurement results are presented to illustrate the topic. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.threat

Threat object classification with a close range polarimetric imaging system by means of H-α decomposition - Adametz, Julian; Schmidt, Lorenz-Peter (International Journal of Microwave and Wireless Technologies, 2014)
lhft_intern.bib::Adametz2014c

THz Measurement Technologies and Applications - Schmidt, Lorenz-Peter; Biber, Stephan; Rehm, Guenther; Huber, Klaus (XIV International Conference on Microwaves, Radar and Wireless Communications, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.thzmea

Tip Clearance Measurement Technique for Stationary Gas Turbines Using an Autofocusing Millimeter-Wave Synthetic Aperture Radar - Schicht, Andreas; Schwarzer, Stefan; Schmidt, Lorenz-Peter (IEEE Transactions on Instrumentation and Measurement, 2012)
In this paper, an autofocusing radar technique is presented for tip clearance measurements in combustion turbines capable of resolving the edges of a typical blade tip. The clearance is determined by measuring the reflection at the blade tip while passing by the antenna, subsequently focusing the data by means of a matched filter operation and interpreting the phase of the blade edge reflection according to the continuous wave radar principle. For this, an autofocus approach was developed, which minimizes defocusing effects and provides an estimate of the clearance as the first result, which is utilized to overcome the phase ambiguity and, thus, to increase the measurement range. The autofocus algorithm applies a weighted phase gradient of the pointlike blade edge reflection as cost function and sensitive indicator for the focal qualit
lhft_intern.bib::Schicht2012

Transmissionsmessung nach Betrag und Phase mit einem homodynen Empfänger im Sub-Millimeterwellen-Bereich - Rehm, Guenther; Schmidt, Lorenz-Peter (Frequenz, 2001)
UnivIS-Import:2015-03-09:Pub.2001.tech.IE.LEH.transm

Untersuchungen zur Eignung heißgeprägter Folien für die Integration von Antennen in Automotive-Exterieurbauteile - Fuchs, Michael; Drummer, Dietmar; Kilian, Andreas; Schmidt, Lorenz-Peter (Zeitschrift Kunststofftechnik, 2009)
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-KT.unters

Unzoned and zoned dielectric lenses for a wide angle scanning antennna - Schmidt, Lorenz-Peter (MIOP `88, 1988)
lhft_intern.bib::Schmidt17

Validation of a fixed tuned planar tripler design optimized for sub-mm wave generation with HBCS devices - Ruf, Marcel; Schür, Jan; Bogdan, N.; Schmidt, Lorenz-Peter; Hartnagel, H. (Proceedings of the European Microwave Association, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.valida

Validation of a Narrowband Signal Processing System for Beam Position Monitoring Purposes in Linear Accelerators - Ruf, Marcel; Trummer, S.; Schmidt, Lorenz-Peter; Setzer, S. (5th German Microwave Conference, 2010)
A new RF frontend for a beam position monitoring system for electron linear accelerators (Linacs) is discussed. The frontend applies a waveguide based input filter section for processing the pulse train, generated by non-interceptive pickups and selection of the desired beam harmonic. Due to increased accuracy, narrowband signal processing was chosen for further signal treatment. Therefore, a two-channel downconverter was designed incorporating two single-balanced diode mixer stages optimized for processing frequencies around 6 GHz, the second beam harmonic in S-Band Linacs. Device characteristics and component validation in a demonstrator with electro-magnetic excitation, simulating beam-induced fields are presented.
lhft_intern.bib::Ruf10

Validation of Electron Beam Position Monitoring Probes by Comparison of Dose Profile Measurements with Beam Displacement Sensing in the Microwave Range - Ruf, Marcel; Schmidt, Lorenz-Peter; Setzer, S. (Asia-Pacific Microwave Conference, 2011)
The development of a beam position monitoring and control architecture for compact linear accelerators requires novel sensors which fulfill the tight space restrictions given in such systems. This paper presents simulation and experimental data of capacitive pickup probes with high sensitivity capable of sensing beam deflections far below 1 mm and compact enough to be integrated in accelerating structures. The correlation of beam position monitoring output signals with dose profile measurements is presented indicating that the proposed compact sensors together with dedicated BPM hardware allow reliable electron beam trajectory determination.
lhft_intern.bib::Ruf11b

Vector Field Measurements at 150 GHz - Weinzierl, Jochen; Brand, Hans; Schmidt, Lorenz-Peter (Proceedings of the 11th Conference and Exhibition on Microwaves, Radio Communication and Electromagnetic Compatibility MIOP 2001, 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.vector

Virtuelle Instrumente in der Praxis - Hrobak, Michael; Schramm, Marcus; Schmidt, Lorenz-Peter; Lechner, Armin (Virtuelle Instrumente in der Praxis, 2009)
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.LEH.virtue

Whisker-Device-Based Optimisation of Fabrication Process for Planar THz Schottky Diodes - Cojocari, O.; Biber, Stephan; Mottet, B.; Rodriguez-Girones, M.; Schmidt, Lorenz-Peter; Hartnagel, H. (3rd ESA Workshop on Millimetre Wave Technology and Applications, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.whiske

Wideband Imaging Systems in the mm-Wave and THz range for Security and Nondestructive Testing - Nezadal, Martin; Adametz, Julian; Schmidt, Lorenz-Peter (31st URSI General Assembly and Scientific Symposium, 2014)
lhft_intern.bib::NezadalURSI2014

Zur Berechnung von transversalen Diskontinuitäten in quasiplanarenMillimeterwellenleitern - Schmidt, Lorenz-Peter (Kleinheubacher Berichte 28, Kleinheubacher Tagung 1984 des U.R.S.I. Landesausschusses Deutschland, 1984)
lhft_intern.bib::Schmidt13

Zur Problematik von MMIC-Schaltungsentwuerfen mit Mikrowellen-CAD-Programmenim Frequenzbereich bis 100 GHz - Schmidt, Lorenz-Peter (URSI-Workshop „Felder und Wellen“, 1992)
lhft_intern.bib::Schmidt26